Vehicle heating part mounting member and vehicle

By utilizing an injection molded product with a thermoplastic resin and carbon fiber filler in vehicle heat generating portion mounting members, the issues of low heat dissipation in conventional materials are addressed, resulting in improved performance and reduced overheating risks.

JP7660000B2Active Publication Date: 2025-04-10SUMITOMO CHEM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021032018
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-13
Filing Date
2021-03-01
Publication Date
2025-04-10
Estimated Expiration
2041-03-01

AI Technical Summary

Technical Problem

Conventional thermoplastic resin compositions used for vehicle heat generating portion mounting members, such as brake rotor bells, exhibit low heat dissipation properties, leading to issues like paper lock phenomena, reduced battery storage capacity and lifetime, and reduced engine cooling effectiveness.

Method used

A vehicle heat generating portion mounting member made from an injection molded product containing a thermoplastic resin and a fibrous inorganic filler, specifically carbon fiber, with a filler content of 30 to 120 parts by mass based on 100 parts by mass of the thermoplastic resin, and with specific heat and thermal conductivity values optimized for improved heat dissipation.

Benefits of technology

The proposed solution enhances the heat dissipation properties of vehicle heat generating portion mounting members, reducing the risk of overheating and improving the performance and longevity of associated components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660000000007
    Figure 0007660000000007
  • Figure 0007660000000008
    Figure 0007660000000008
  • Figure 0007660000000009
    Figure 0007660000000009
Patent Text Reader

Abstract

To provide a vehicle heat generating part fitting member that is made of a resin and has high-thermal radiation property, and to provide a vehicle in which the vehicle heat generating part fitting member is fitted to a heat generating part.SOLUTION: A vehicle heat generating part fitting member is a fitting member to be fitted to a heat generating part of a vehicle and includes an injection molding that contains a thermoplastic resin and a fibrous inorganic filler.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a vehicle heat generating part mounting member and a vehicle. [Background technology]

[0002] In recent years, in the field of transportation equipment, including automobiles and aircraft, efforts are being made to reduce the weight of parts in order to improve fuel efficiency. In order to reduce the weight of parts, the use of resin materials instead of current metal materials for the materials of each part is being considered. For example, by using thermoplastic resins as molding materials for automobile frame members, suspension members, shock absorbing members, etc., automobiles that are lighter than current products can be obtained.

[0003] On the other hand, as for mounting members used in heat generating parts of a vehicle, the current situation is that metal materials have not yet been replaced by resin materials. For example, brake rotor bells, which secure disc-shaped brake rotors, are generally made of aluminum, which has high thermal conductivity, because they are able to effectively dissipate heat generated by friction between the brake rotor and brake pads during braking. Furthermore, as shown in Patent Document 1, disc-shaped brake rotors are also generally made of metal materials that have high thermal conductivity and mechanical strength. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2017-519954 Summary of the Invention [Problem to be solved by the invention]

[0005] When attempting to use conventional molding materials such as thermoplastic resin compositions as mounting members for the above-mentioned heat generating parts of a vehicle, various problems arise. For example, when a brake rotor bell is manufactured using a molding material such as a conventional thermoplastic resin composition, the heat dissipation property of the brake rotor bell is low, and there is a risk of the paper lock phenomenon occurring. Furthermore, when molding materials such as conventional thermoplastic resin compositions are used as battery mounting members, they may cause a decrease in the battery's charge storage capacity and lifespan.When molding materials such as conventional thermoplastic resin compositions are used as engine mounting members (engine peripheral members), they may cause the engine to overheat due to a reduced engine cooling effect.

[0006] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a vehicle heat-generating part mounting member made of resin with high heat dissipation properties, and a vehicle in which the vehicle heat-generating part mounting member is attached to a heat-generating part. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention employs the following configuration. [1] A mounting member to be attached to a heat generating part of a vehicle, the mounting member comprising an injection molded product containing a thermoplastic resin and a fibrous inorganic filler. [2] The vehicle heating part mounting member according to [1], wherein the fibrous inorganic filler is carbon fiber. [3] The mounting member for a vehicle heat generating part according to [1] or [2], wherein a content of the fibrous inorganic filler is 30 to 120 parts by mass relative to a total amount (100 parts by mass) of the thermoplastic resin. [4] The mounting member for a vehicle heat generating part according to any one of [1] to [3], wherein the injection-molded article has a specific heat at 23°C of 0.92 to 1.50 J / g K as measured in accordance with JIS K7123:2012. [5] The vehicle heat generating part mounting member according to any one of [1] to [4], wherein the injection molded product has a specific heat of 1.00 to 2.00 J / g·K at 150°C, measured in accordance with JIS K7123:2012. [6] The vehicle heat generating part mounting member according to any one of [1] to [5], wherein the injection molded article has a thermal conductivity of 0.20 to 10 W / mK as measured in accordance with ASTM E-1461. [7] The vehicle heat generating part mounting member according to any one of [1] to [6], wherein the injection molded product has a primary resonance frequency of 260 Hz or more. [8] The vehicle heat generating part mounting member according to [7], wherein the injection molded product has a primary resonance frequency of 300 to 400 Hz. [9] The vehicle heat generating part mounting member according to any one of [1] to [8], wherein the injection molded product has an emissivity of 0.80 or more.

[10] The vehicle heat generating part mounting member according to any one of [1] to [9], which is used as a peripheral member of a brake rotor.

[11] The vehicle heat generating part mounting member according to any one of [1] to

[10] , which is used as a brake rotor bell.

[12] A vehicle having a vehicle heat generating part mounting member according to any one of [1] to

[11] mounted to a heat generating part.

[13] A vehicle heat generating part mounting member, which is made of resin and is to be attached to a heat generating part of a vehicle, and has an emissivity of 0.80 or more. Effect of the Invention

[0008] According to the present invention, it is possible to provide a vehicle heat generating part mounting member made of resin having high heat dissipation properties, and a vehicle in which the vehicle heat generating part mounting member is mounted to a heat generating part. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram illustrating an embodiment of a disc brake. [Diagram 2] FIG. 1 is a schematic diagram illustrating one embodiment of a brake rotor bell. [Diagram 3] 1 is a cross-sectional view of a mold preferably used for manufacturing a brake rotor bell 1 of an embodiment. [Figure 4] 1 is a schematic diagram for explaining a method for manufacturing a brake rotor bell 1 using a mold 100. FIG. [Diagram 5] 1 is a schematic diagram for explaining a method for manufacturing a brake rotor bell 1 using a mold 100. FIG. [Figure 6] FIG. 2 is a schematic diagram showing an example of a resin pellet manufacturing apparatus. [Figure 7] FIG. 2 is a schematic diagram showing measurement points A and B when conducting a heat dissipation test of a brake rotor bell. [Figure 8] 4 is a graph showing evaluation results of heat dissipation properties at measurement point A of the brake rotor bells of Examples 1 to 4 and the brake rotor bell of Comparative Example 1. [Figure 9] 4 is a graph showing evaluation results of heat dissipation properties at measurement point B of the brake rotor bells of Examples 1 to 4 and the brake rotor bell of Comparative Example 1. [Figure 10] 1 is a graph showing the evaluation results of the EMI shielding characteristics (dB) of the test pieces of Reference Examples 8, 12, and 13 in an electric field wave of each frequency under measurement condition X. [Figure 11] 13 is a graph showing the evaluation results of the EMI shielding characteristics (dB) of the test pieces of Reference Examples 8, 12, and 13 in a magnetic field wave of each frequency under measurement condition X. [Figure 12] 13 is a graph showing the evaluation results of the EMI shielding characteristics (dB) of the test pieces of Reference Examples 8, 12, and 13 in an electric field wave of each frequency under measurement condition Y. [Figure 13] 13 is a graph showing the evaluation results of the EMI shielding characteristics (dB) of the test pieces of Reference Examples 8, 12, and 13 in a magnetic field wave of each frequency under measurement condition Y. [Figure 14] 4 is a graph showing temperature changes of the brake rotor bells of the embodiment and the comparative example during driving. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] (Mounting material for heating parts of vehicles) A first aspect of the present invention is a mounting member for a heat generating part of a vehicle. The vehicle heat generating part mounting member is a mounting member to be mounted on a heat generating part of a vehicle, and includes an injection molded product containing a thermoplastic resin and a fibrous inorganic filler. The vehicle heat generating part mounting member is characterized by being made of resin. For example, the injection molded product included in the vehicle heat generating part mounting member is made of a resin composition containing a thermoplastic resin and a fibrous inorganic filler as a molding material.

[0011] In this specification, a mounting member does not mean a member that has a function as a vehicle member, such as an engine mount (a member that reduces the transmission of vibrations to the vehicle body), but rather a member that is attached directly or indirectly to a part having such a function in order to fix and support the part having such a function.

[0012] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings as needed. In the drawings, the same or corresponding parts are denoted by the same or corresponding reference numerals, and duplicate explanations will be omitted. In addition, the dimensional ratios in each drawing are exaggerated for the purpose of explanation, and do not necessarily correspond to the actual dimensional ratios.

[0013] First Embodiment The first embodiment of the present invention is a brake rotor bell to be attached to a brake rotor (heat generating portion). The brake rotor bell is an injection molded product, and is made of a resin composition containing a thermoplastic resin and a fibrous inorganic filler as a molding material.

[0014] FIG. 1 is a schematic diagram of a disc brake 7 equipped with a brake rotor bell 1 . The disc brake 7 includes a brake rotor bell 1 , a brake rotor 2 , an axle 3 and a brake pad 4 .

[0015] The disc brake 7 is configured such that a brake rotor 2 is sandwiched between a connecting part (not shown) and a brake rotor bell 1, and an axle 3 is inserted and fixed through the center of the brake rotor bell 1, the brake rotor 2, and the connecting part.

[0016] The disc brake 7 rotates integrally with the wheel, and generates a braking force by pinching the brake rotor 2 with the brake pads 4 during braking.

[0017] In this specification, the direction in which the axis of the axle 3 extends is referred to as the axial direction, the direction intersecting the axial direction of the axle 3 is referred to as the radial direction, and the direction going around the axis of the axle 3 is referred to as the circumferential direction.

[0018] The connecting portion is formed in a disk shape arranged coaxially with the axis of the axle 3. A pin protruding in the axial direction (toward the brake rotor 2) is formed on the outer periphery of the connecting portion. A plurality of pins (for example, four) are formed at intervals in the circumferential direction.

[0019] The brake rotor 2 has an outer diameter larger than that of the connecting portion, and is an annular member when viewed in the axial direction. The brake rotor 2 is overlapped with the connecting portion in the axial direction with the outer circumferential portion projecting radially beyond the connecting portion.

[0020] In this specification, the term "annular" refers only to a shape that is annular when viewed in the axial direction, and various shapes can be adopted for the thickness and unevenness in the axial direction. For example, the term "annular" in this specification includes a flat plate shape when viewed in the radial direction, and a cylindrical shape extending in the axial direction.

[0021] Brake rotor bell 1 is formed in an annular shape when viewed in the axial direction, and protrudes so as to be curved outward in the axial direction (the opposite side to brake rotor 2). The brake rotor bell 1 is overlapped with the brake rotor 2 in the axial direction. The diameter of the brake rotor bell 1 is, for example, 100 to 500 mm.

[0022] FIG. 2 is a schematic diagram of the brake rotor bell 1. Brake rotor bell 1 comprises a base portion 10 having a circular ring shape when viewed in the axial direction, and a flange portion 11 that projects radially outward from the axially inner end (brake rotor 2 side) of base portion 10.

[0023] The base portion 10 protrudes so as to be curved outward in the axial direction (the side opposite to the brake rotor 2), and includes a top wall portion and a side wall portion. The diameter of the base portion 10 is, for example, 50 to 400 mm. The axial height of the base portion 10 (the axial height of the top wall portion and the side wall portion) is, for example, 10 to 50 mm. The axial thickness of the top wall of the base portion 10 (the distance between the front and back of the top wall of the base portion 10) is, for example, 1 to 20 mm.

[0024] The flange portion 11 protrudes outward from the end portion of the base portion 10 in the radial direction by, for example, 1 to 30 mm. The axial thickness of the flange portion 11 is, for example, 1 to 20 mm.

[0025] In the base portion 10, a first through hole 12 is formed in a portion located on the axis line, penetrating the base portion 10 in the axial direction. The first through hole 12 may be formed with a metal collar inserted therein. Note that using a metal collar provides better thermal stability. Also, from the viewpoints of dimensional accuracy, cutting costs such as post-processing, and durability against the tightening load torque of the screw during fixing, it is preferable to use a metal collar.

[0026] In the base portion 10, a second through hole 13 is formed in a portion located around the first through hole 12, penetrating the base portion 10 in the axial direction. A plurality of second through holes 13 (for example, four) are formed at intervals in the circumferential direction. The second through hole 13 may be formed with a metal collar inserted therein. Note that using a metal collar provides better stability against heat. Also, from the viewpoints of dimensional accuracy, cutting costs such as post-processing, and durability against the tightening load torque of the screw during fixing, it is preferable to use a metal collar.

[0027] The flange portion 11 is formed with a third through hole 14 penetrating the flange portion 11 in the axial direction. A plurality of (e.g., eight) third through holes 14 are formed at intervals in the circumferential direction. The third through hole 14 may be formed with a metal collar inserted therein. Note that using a metal collar provides better thermal stability. Also, from the viewpoints of dimensional accuracy, cutting costs such as post-processing, and durability against the tightening load torque of the screw during fixing, it is preferable to use a metal collar.

[0028] As shown in FIGS. 1 and 2, a brake rotor bell 1 is a vehicle heat generating part mounting member that is mounted on a brake rotor 2, which is a heat generating part.

[0029] In the base portion 10, a second through hole 13 is formed in a portion located around the first through hole 12, penetrating the base portion 10 in the axial direction (see FIG. 2). A plurality of second through holes 13 (for example, four) are formed at intervals in the circumferential direction (see FIG. 2). A pin of the connecting portion is inserted through the second through hole 13 via the brake rotor 2. A nut is fastened to a portion of the connecting portion pin that protrudes axially outward (opposite side to the brake rotor 2) relative to the brake rotor bell 1 (see FIG. 1). This fixes the brake rotor bell 1 and the connecting portion. The brake rotor 2 is also fixed by being sandwiched between the brake rotor bell 1 and the connecting portion. From the standpoint of stability during installation, it is preferable that the second through holes 13 are arranged at regular intervals in the circumferential direction.

[0030] A third through hole 14 is formed in the flange portion 11, penetrating the flange portion 11 in the axial direction. A plurality of third through holes 14 (e.g., eight) are formed at intervals in the circumferential direction (see FIG. 2). A bolt is inserted into the third through hole 14 (see FIG. 1). The brake rotor bell 1 and the brake rotor 2 are fixed together by the bolt. From the standpoint of stability during installation, it is preferable that the third through holes 14 are arranged at regular intervals in the circumferential direction.

[0031] The specific heat of brake rotor bell 1 at 23° C. is preferably 0.92 J / g·K or more, more preferably 0.95 J / g·K or more, and even more preferably 1.00 J / g·K or more.

[0032] Furthermore, the specific heat of brake rotor bell 1 at 23° C. is preferably 1.50 J / g·K or less, more preferably 1.10 J / g·K or less, and even more preferably 1.08 J / g·K or less.

[0033] For example, the specific heat of the brake rotor bell 1 at 23° C. is preferably 0.92 to 1.50 J / g·K, more preferably 0.95 to 1.10 J / g·K, and even more preferably 1.00 to 1.08 J / g·K.

[0034] The specific heat of brake rotor bell 1 at 150° C. is preferably 1.00 J / g·K or more, and more preferably 1.30 J / g·K or more.

[0035] Furthermore, the specific heat of brake rotor bell 1 at 150° C. is preferably 2.00 J / g·K or less, more preferably 1.70 J / g·K or less, and even more preferably 1.50 J / g·K or less.

[0036] For example, the specific heat of the brake rotor bell 1 at 150° C. is preferably 1.00 to 2.00 J / g·K, more preferably 1.00 to 1.70 J / g·K, and even more preferably 1.30 to 1.50 J / g·K.

[0037] If the specific heat of the brake rotor bell 1 is equal to or greater than the above-mentioned preferable lower limit, the temperature rise of the brake rotor bell during braking can be further suppressed, and deterioration of the resin that constitutes the brake rotor bell 1 can be further suppressed. If the specific heat of the brake rotor bell 1 is equal to or less than the above-mentioned preferable upper limit value, the heat dissipation to the outside air is further improved.

[0038] In this specification, "specific heat" refers to a value measured in accordance with JIS K7123:2012 using a specific heat analysis program (manufactured by Shimadzu Corporation; product name "DSC-60A Plus").

[0039] The brake rotor bell 1 preferably has a thermal conductivity of 0.20 W / mK or more, more preferably 0.30 W / mK or more, and even more preferably 0.35 W / mK or more.

[0040] Furthermore, the brake rotor bell 1 preferably has a thermal conductivity of 10 W / mK or less, more preferably 5 W / mK or less, and even more preferably 1 W / mK or less.

[0041] For example, the thermal conductivity of the brake rotor bell 1 is preferably 0.20 to 10 W / mK, more preferably 0.30 to 5 W / mK, and even more preferably 0.35 to 1 W / mK.

[0042] If the thermal conductivity of the brake rotor bell 1 is equal to or greater than the above-mentioned preferable lower limit, heat can be easily removed from the brake rotor, and the cooling performance of the brake rotor is further improved. If the thermal conductivity of the brake rotor bell 1 is equal to or less than the above-mentioned preferable upper limit value, deterioration of the resin constituting the brake rotor bell 1 can be further suppressed.

[0043] In this specification, "thermal conductivity" refers to a value measured in accordance with ASTM E-1461 at 23° C. using a xenon flash analyzer (manufactured by Advance Riko Co., Ltd.; product name "TC-7000").

[0044] Brake rotor bell 1 preferably has a specific heat at 23°C of 0.92 to 1.50 J / g·K and a thermal conductivity of 0.20 to 10 W / mK, more preferably has a specific heat at 23°C of 0.95 to 1.10 J / g·K and a thermal conductivity of 0.30 to 5 W / mK, and even more preferably has a specific heat at 23°C of 1.00 to 1.08 J / g·K and a thermal conductivity of 0.35 to 1 W / mK.

[0045] Brake rotor bell 1 preferably has a specific heat at 150°C of 1.00 to 2.00 J / g·K and a thermal conductivity of 0.20 to 10 W / mK, more preferably has a specific heat at 150°C of 1.00 to 1.70 J / g·K and a thermal conductivity of 0.30 to 5 W / mK, and even more preferably has a specific heat at 150°C of 1.30 to 1.50 J / g·K and a thermal conductivity of 0.35 to 1.00 W / mK.

[0046] The primary resonance frequency of the brake rotor bell 1 is preferably 260 Hz or higher, more preferably 280 Hz or higher, and even more preferably 300 Hz or higher.

[0047] The primary resonance frequency of the brake rotor bell 1 is preferably 450 Hz or less, more preferably 420 Hz or less, and even more preferably 400 Hz or less.

[0048] For example, the primary resonance frequency of the brake rotor bell 1 is preferably 260 Hz or more and 450 Hz or less, more preferably 280 Hz or more and 420 Hz or less, and even more preferably 300 Hz or more and 400 Hz or less.

[0049] Road noise (noise generated when driving on a road with a rough surface or bumps and joints) has a particularly loud frequency of 100 to 250 Hz. Therefore, in order to further avoid resonance with road noise, it is preferable that the primary resonance frequency of the brake rotor bell 1 is 260 Hz or higher. In order to further avoid resonance with other noises (engine noise, gear noise), it is preferable that the primary resonance frequency of the brake rotor bell 1 is 450 Hz or lower.

[0050] In this specification, the "primary resonant frequency" refers to a value determined by the following measurement method. (1) An aluminum plywood 10 mm x 80 mm x 2 mm is fixed to the workpiece at the tip of the vibration force detector built into the impedance head of the vibration exciter (power amplifier / model 371-A) in the impedance device (Ono Sokki Co., Ltd.; mass cancellation amplifier: mass cancellation amplifier MA-5500; channel data station: DS-2100). The center of the brake rotor bell 1 is positioned so that it is hooked onto the fixed aluminum plywood. (2) After that, vibration is applied to the tip of the above-mentioned excitation force detector at room temperature (23°C) in the frequency range of 0 to 2000 Hz, and the excitation force and acceleration waveform at the excitation point are detected, thereby performing a resonance test using the central excitation method. (3) The mechanical impedance at the excitation point is calculated based on the obtained excitation force and the velocity signal obtained by integrating the acceleration signal. The frequency at which the first peak appears on the impedance curve obtained with the horizontal axis as frequency and the vertical axis as mechanical impedance is determined as the primary resonant frequency.

[0051] The specific heat, thermal conductivity and primary resonant frequency of the brake rotor bell 1 can be controlled, for example, by the type of thermoplastic resin and fibrous inorganic filler that are the molding materials of the brake rotor bell 1 described below, the fiber diameter and fineness of the fibrous inorganic filler, and the content of each component.

[0052] Regarding the primary resonance frequency, for example, when the thermoplastic resin that is the molding material of the brake rotor bell 1 is liquid crystal polyester, the liquid crystal polyester has a multi-layer structure (a core layer in which the liquid crystal polyester molecules are not oriented; a skin layer in which the liquid crystal polyester molecules are oriented), so that the primary resonance frequency can be made higher than when other thermoplastic resins are used.

[0053] The emissivity of the brake rotor bell 1 is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and particularly preferably 0.94 or more. The upper limit of the emissivity of the brake rotor bell 1 is not particularly limited, but since the emissivity of an ideal black body (an ideal object that absorbs 100% of infrared rays and emits 100% of infrared rays) is 1, the upper limit of the emissivity of the brake rotor bell 1 is less than 1. That is, the emissivity of the brake rotor bell 1 is preferably 0.80 or more and less than 1, more preferably 0.85 or more and less than 1, even more preferably 0.90 or more and less than 1, and particularly preferably 0.94 or more and less than 1.

[0054] If the emissivity of the brake rotor bell 1 is equal to or greater than the above-mentioned preferable lower limit, the brake rotor bell 1 cools more easily, and the cooling performance of the brake rotor is further improved.

[0055] In this specification, "emissivity" refers to the amount of infrared radiation emitted from an object; an ideal black body has an emissivity of 1, while a perfect reflector (an ideal object that does not absorb any infrared radiation) has an emissivity of 0. In this specification, the "emissivity" of a measurement object (for example, the brake rotor bell 1) is a value calculated by the following formula (e-1). In formula (e-1), W' is the energy radiated by the object being measured. W is the ideal total radiant energy based on an ideal black body. In this specification, W' means a value calculated from the absolute temperature (T') calculated from the temperature (°C) measured within a range of 30 cm from the object to be measured using a non-contact thermometer (for example, product name "IT-500L" manufactured by Horiba, Ltd.) using the following formula (e-2). In this specification, W means a value calculated from the absolute temperature (T) calculated from the temperature (°C) measured with a contact thermometer (e.g., product name "DT-510" manufactured by HOZAN CORPORATION) using the following formula (e-3). In the following equations (e-2) and (e-3), σ is the Stefan-Boltzmann constant (5.67×10 -8 ). Emissivity ε=W' / W···(e-1) W'=σT' 4 (e-2) W = σT 4 (e-3)

[0056] Furthermore, when an aluminum die-cast (ADC12) is machined to produce a brake rotor bell A having the same shape as brake rotor bell 1, and the emissivity of brake rotor bell 1 and brake rotor bell A at portion A shown in FIG. 7 is calculated, it is preferable that (emissivity of brake rotor bell 1 / emissivity of brake rotor bell A (εp / εa)) is 1.0 or more, more preferably 1.2 or more, even more preferably 1.3 or more, and particularly preferably 1.8 or more.

[0057] When εp / εa is equal to or greater than the above-mentioned preferable lower limit, the brake rotor bell 1 cools more easily, and the cooling performance of the brake rotor is further improved.

[0058] In brake rotor bell 1, it is preferable that the EMI (Electro Magnetic Interference) shielding characteristics of brake rotor bell 1 are equivalent to the EMI shielding characteristics of brake rotor bell A having the same shape as brake rotor bell 1, which is manufactured by processing aluminum die casting (ADC12).

[0059] The EMI shielding characteristics of the brake rotor bell 1 and the brake rotor bell A can be measured, for example, by the Advantest method. The Advantest method is a standard measurement method for evaluating EMI shielding characteristics. Specifically, in a shielding box, electromagnetic waves (electric field waves and magnetic field waves) of a specific frequency are emitted from one side, and the electric field waves and magnetic field waves that pass through an object to be measured (for example, the brake rotor bell 1) are received from the other side, and the attenuation (shielding characteristics) of the electromagnetic waves (electric field waves and magnetic field waves) caused by passing through the object to be measured is measured. For example, the shielding characteristics (dB) of the electric field waves and magnetic field waves in the frequency range of 30 to 1000 MHz can be measured. The above measurements can be performed using, for example, a plastic shielding material evaluation device (product name: TR17301A, manufactured by Advantest Corporation), an EMI test receiver (product name: R&S (registered trademark) ESR3, manufactured by Rohde & Schwarz), and an AMPLIFIER (product name: 8447D preamplifier, manufactured by Keysight Technologies).

[0060] For brake rotor bell 1, when the measurement conditions are a resolution bandwidth (RBW) of 50 MHz, a video bandwidth (VBW) of 50 MHz, and a sweep time (SWP) of 1 s, it is preferable that the EMI shielding characteristic (dB) of brake rotor bell 1 / the EMI shielding characteristic (dB) of brake rotor bell A for electric field waves and magnetic field waves in each frequency range (hereinafter also referred to as the "shielding characteristic ratio") is greater than or equal to the following value:

[0061] That is, in the brake rotor bell 1, the shielding characteristic ratio of a 30 MHz electric field wave is preferably 0.3 or more, more preferably 0.4 or more, and even more preferably 0.45 or more. Also, the shielding characteristic ratio of a 100 MHz electric field wave is preferably 0.5 or more, more preferably 0.55 or more, and even more preferably 0.9 or more. Furthermore, the shielding characteristic ratio for an electric field wave of 200 MHz is preferably 0.3 or more, more preferably 0.8 or more, and even more preferably 0.9 or more. Furthermore, the shielding characteristic ratio for an electric field wave of 300 MHz is preferably 0.3 or more, more preferably 0.6 or more, and even more preferably 0.75 or more. Furthermore, the shielding characteristic ratio for an electric field wave of 500 MHz is preferably 0.3 or more, more preferably 0.6 or more, and even more preferably 0.75 or more. Furthermore, the shielding characteristic ratio for an electric field wave of 1000 MHz is preferably 0.15 or more, more preferably 0.6 or more, and even more preferably 0.75 or more.

[0062] In the brake rotor bell 1, the shielding characteristic ratio for a 30 MHz magnetic field wave is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more. Furthermore, the shielding characteristic ratio for a 100 MHz magnetic field wave is preferably 0.3 or more, more preferably 0.4 or more, and even more preferably 0.45 or more. Furthermore, the shielding characteristic ratio for a 200 MHz magnetic field wave is preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 0.65 or more. Moreover, the shielding characteristic ratio for a 300 MHz magnetic wave is preferably 0.3 or more, more preferably 0.6 or more, and even more preferably 0.75 or more. Furthermore, the shielding characteristic ratio for a 500 MHz magnetic field wave is preferably 0.3 or more, more preferably 0.6 or more, and even more preferably 0.8 or more. Furthermore, the shielding characteristic ratio for a 1000 MHz magnetic field wave is preferably 0.3 or more, more preferably 0.6 or more, and even more preferably 0.7 or more.

[0063] For brake rotor bell 1, when the measurement conditions are a resolution bandwidth (RBW) of 1 kHz, a video bandwidth (VBW) of 300 Hz, and a sweep time (SWP) of 35 s, it is preferable that the EMI shielding characteristic (dB) of brake rotor bell 1 / the EMI shielding characteristic (dB) of brake rotor bell A for electric field waves and magnetic field waves in each frequency range (hereinafter also referred to as the "shielding characteristic ratio") is greater than or equal to the following value.

[0064] That is, in the brake rotor bell 1, the shielding characteristic ratio of a 30 MHz electric field wave is preferably 0.2 or more, more preferably 0.9 or more, and even more preferably 0.95 or more. Also, the shielding characteristic ratio of a 100 MHz electric field wave is preferably 0.3 or more, more preferably 0.9 or more, and even more preferably 1.0 or more. Furthermore, the shielding characteristic ratio for an electric field wave of 200 MHz is preferably 0.3 or more, more preferably 0.9 or more, and even more preferably 0.95 or more. Furthermore, the shielding characteristic ratio for an electric field wave of 300 MHz is preferably 0.2 or more, more preferably 0.8 or more, and even more preferably 0.9 or more. Furthermore, the shielding characteristic ratio for an electric field wave of 500 MHz is preferably 0.2 or more, more preferably 0.9 or more, and even more preferably 0.95 or more. Furthermore, the shielding characteristic ratio for an electric field wave of 1000 MHz is preferably 0.15 or more, more preferably 0.6 or more, and even more preferably 0.9 or more.

[0065] In the brake rotor bell 1, the shielding characteristic ratio for a 30 MHz magnetic field wave is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more. Furthermore, the shielding characteristic ratio for a 100 MHz magnetic field wave is preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 0.55 or more. Furthermore, the shielding characteristic ratio for a 200 MHz magnetic field wave is preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 0.7 or more. Furthermore, the shielding characteristic ratio for a 300 MHz magnetic field wave is preferably 0.6 or more, more preferably 0.8 or more, and even more preferably 0.85 or more. Furthermore, the shielding characteristic ratio for a 500 MHz magnetic field wave is preferably 0.3 or more, more preferably 0.6 or more, and even more preferably 0.9 or more. Furthermore, the shielding characteristic ratio for a 1000 MHz magnetic field wave is preferably 0.6 or more, more preferably 0.9 or more, and even more preferably 0.95 or more.

[0066] In the brake rotor bell 1, if the shielding characteristic ratio for electric field waves and magnetic field waves of the above frequencies under each of the above measurement conditions is equal to or greater than the above preferred value, for example, when the electric parking brake is activated, electromagnetic noise from the motor near the brake is reduced, making it possible to shorten the operating time and save energy. In addition, it can reduce electromagnetic noise from near the brakes when the adaptive cruise control (ACC) is activated, improving the sensitivity of other sensor devices.

[0067] The upper limit of the shielding characteristic ratio for electric field waves and magnetic field waves of the above frequencies is not particularly limited, and is, for example, 2.0 or less.

[0068] <Brake rotor bell 1 manufacturing method> The brake rotor bell 1 is manufactured by injection molding. The form of the resin composition containing a thermoplastic resin and a fibrous inorganic filler, which is the molding material of the brake rotor bell 1, is not particularly limited, and examples thereof include a mixture of a thermoplastic resin and a fibrous inorganic filler; a mixture of a thermoplastic resin, a fibrous inorganic filler, and other components; and resin pellets (hereinafter also referred to as resin pellets) obtained by impregnating a molten material obtained by melt-kneading a thermoplastic resin and, if necessary, other components into a fibrous inorganic filler and pelletizing the resulting material.

[0069] Of the above, the resin composition that is the molding material for the brake rotor bell 1 is preferably a resin pellet, from the viewpoint of being able to perform injection molding while maintaining the fiber length of the fibrous inorganic filler, and more preferably a resin pellet obtained by the method described below.

[0070] A method for manufacturing the brake rotor bell 1 by injection molding will be described below together with an explanation of a mold 100 that is preferably used for manufacturing the brake rotor bell 1.

[0071] FIG. 3 is a cross-sectional view of a mold 100 preferably used for manufacturing the brake rotor bell 1 of this embodiment, and is a cross-sectional view corresponding to FIG.

[0072] 3 has a first member 101 and a second member 102. A parting line 109 is formed at the position where the first member 101 and the second member 102 are joined together.

[0073] The mold 100 has a cavity 110, a gate 120, a runner 130, and a sprue 140.

[0074] Cavity 110 is a space having a shape corresponding to the injection-molded product to be molded. The injection-molded product molded in cavity 110 can be removed by, for example, dividing mold 100 into two parts, an upper part and a lower part, at parting line 109.

[0075] Gate 120 is provided at a position corresponding to the inner circumferential surface of brake rotor bell 1, over the entire circumference of the inner circumferential surface.

[0076] The height hg of the gate 120 is preferably 5% or more of the height hc of the cavity 110, more preferably 10% or more, and even more preferably 15% or more. Moreover, the height hg of the gate 120 is preferably 50% or less of the height of the cavity 110, more preferably 30% or less, and further preferably 20% or less.

[0077] For example, the height hg of the gate 120 is preferably 5% to 50% of the height of the cavity, more preferably 10% to 30%, and even more preferably 15% to 20%. The height hg of the gate 120 is, for example, 1.5 to 15 mm.

[0078] The height hg of the gate 120 refers to the distance between parallel lines inscribed in the first member 101 and the second member 102 in the gate 120.

[0079] The runner 130 is provided on the inner periphery side of the brake rotor bell 1 over the entire inner periphery of the brake rotor bell 1 and is connected to the gate 120 . The gate 120 and the runner 130 are so-called diaphragm gates. The runner 130 has a slug well 131 . The slug well 131 is formed in the second member 102 .

[0080] The height hs of the slug well 131 is preferably 50% or more of the height hc of the cavity 110, more preferably 70% or more, and even more preferably 90% or more. Furthermore, the height hs of slug well 131 is preferably 200% or less of the height hc of cavity 110, more preferably 150% or less, and even more preferably 130% or less.

[0081] If the height hs of the slug well 131 is within the above-mentioned preferred range, the resin solidified at the nozzle tip of the injection molding machine will be less likely to flow into the cavity 110, making it easier for the molten resin composition (hereinafter also referred to as molten resin MR) to flow.

[0082] For example, the height hs of slug well 131 is preferably 50% to 200% of the height hc of cavity 110, more preferably 70% to 150%, and even more preferably 90% to 130%. For example, the height hc of the cavity 110 is 5 to 30 mm. For example, the height hs of the slug well 131 is 5 to 30 mm.

[0083] The height hc of the cavity 110 refers to the maximum distance between parallel lines inscribed in the first member 101 and the second member 102 at the position where the height inside the cavity 110 is measured.

[0084] The height hs of slug well 131 refers to the distance between the bottom surface of slug well 131 and an extension of a line inscribed on the runner 130 side of first component 101 in the opposing direction of first component 101 and second component 102.

[0085] The sprue 140 is provided so as to penetrate the first member 101 in the thickness direction of the first member 101, and is connected to the runner 130. In the injection molding machine 1000, the molten resin MR is poured into the mold 100 through the sprue 140.

[0086] That is, the mold 100 used in manufacturing the brake rotor bell 1 of this embodiment preferably satisfies the following (1) to (3). (1) In a cavity 110 shaped to correspond to the brake rotor bell 1 , a diaphragm gate (gate 120 and runner 130 ) is provided on the inner periphery of the brake rotor bell 1 . (2) The height hs of slug well 131 connected to gate 120 is 50% or more and 200% or less of the height hc of cavity 110. (3) The height hg of the gate 120 is smaller than the height hc of the cavity 110.

[0087] 4 and 5 are schematic diagrams showing the state in which the brake rotor bell 1 is manufactured using the mold 100. The white arrows in the drawings typically indicate the flow direction of the molten resin MR.

[0088] As shown in FIG. 4, when molten resin MR is injected into the mold 100 from an injection molding machine 1000, the molten resin MR flows into the runner 130 via the sprue 140.

[0089] Next, as shown in FIG. 5, when the filling of the runner 130 and the slug well 131 with the molten resin MR is completed, the molten resin MR flows into the cavity 110 through the gate 120.

[0090] Here, when the height hs of the slug well 131 is 50% or more and 200% or less of the height hc of the cavity 110, pressure loss of the molten resin MR is less likely to occur in the runner 130 than in the cavity 110, and pressure loss is easier to suppress. As a result, in the mold 100, a difference is more likely to occur between the internal pressure of the molten resin MR in the runner 130 and the internal pressure of the molten resin MR in the cavity 110.

[0091] Therefore, according to the manufacturing method using the mold 100, it is possible to ensure a sufficient pressure holding for the molten resin MR in the cavity 110, and to perform good injection molding.

[0092] Thereafter, the mold 100 is divided into two parts, an upper part and a lower part, at the parting line 109, so that the injection molded product can be removed. The brake rotor bell 1 can then be manufactured by drilling a hole in the center of the injection molded product to form the first through hole 12.

[0093] In addition, the second through hole 13 and the third through hole 14 may be formed by the shape of a mold, or by performing insert molding using a metal collar to form the second through hole 13 and the third through hole 14 by the collar.

[0094] The brake rotor bell 1 of this embodiment includes an injection molded product containing a thermoplastic resin and a fibrous inorganic filler. Because the brake rotor bell 1 contains the fibrous inorganic filler, it is possible to achieve both mechanical strength and heat dissipation. In addition, because the inorganic filler is fibrous, it is possible to create a heat conduction path in the orientation direction of the fibers, making it easy to control the direction of heat transfer. As described above, the brake rotor bell 1 of this embodiment has excellent heat dissipation properties and is lighter than conventional metal brake rotor bells.

[0095] <Other embodiments> Although the brake rotor bell 1 has been described as the first embodiment of the present invention, the vehicle heat generating part mounting member of this embodiment is not limited to the brake rotor bell.

[0096] Specific examples of vehicle heat-generating part mounting components in this embodiment include knuckles, knuckle arms, hubs, hub bolts, hub nuts, hub carriers, crank bolts, bleeder caps, bleeder screws, cylinder bodies, mounting brackets, pad clips, shims, piston boots, leading shoes, trailing shoes, back plates, front plates, drums, dust covers, caliper brackets, fulcrum shafts, bell hats, brake boosters, front uprights, rear uprights, and other brake rotor peripheral components (support components around the brake rotor); radiator peripheral components (components for fixing the radiator), such as radiator supports; engine peripheral components (support components around the engine); battery peripheral components (support components around the battery), and the like.

[0097] The vehicle heat generating part mounting member of this embodiment preferably has a specific heat at 23°C of 0.4 J / g·K or more, more preferably 0.6 J / g·K or more, and even more preferably 0.8 J / g·K or more.

[0098] Furthermore, the vehicle heat generating part mounting member of this embodiment preferably has a specific heat at 23°C of 2.0 J / g·K or less, more preferably 1.6 J / g·K or less, and even more preferably 1.2 J / g·K or less.

[0099] The vehicle heat generating part mounting member of this embodiment preferably has a specific heat at 150°C of 0.4 J / g·K or more, more preferably 0.7 J / g·K or more, and even more preferably 0.9 J / g·K or more.

[0100] Furthermore, the vehicle heat generating part mounting member of this embodiment preferably has a specific heat at 150°C of 2.5 J / g·K or less, more preferably 2.2 J / g·K or less, and even more preferably 1.8 J / g·K or less.

[0101] When the specific heat of the vehicle heat generating part mounting member of this embodiment is equal to or greater than the above-mentioned preferable lower limit, deterioration of the resin constituting the vehicle heat generating part mounting member can be further suppressed. If the specific heat of the vehicle heat generating part mounting member of this embodiment is equal to or less than the above-mentioned preferable upper limit value, the heat dissipation property is further improved.

[0102] For example, the specific heat of the vehicle heat generating part mounting member of this embodiment at 23° C. is preferably 0.4 to 2.0 J / g·K, more preferably 0.6 to 1.6 J / g·K, and even more preferably 0.8 to 1.2 J / g·K.

[0103] For example, the specific heat of the vehicle heat generating part mounting member of this embodiment at 150° C. is preferably 0.4 to 2.5 J / g·K, more preferably 0.7 to 2.2 J / g·K, and even more preferably 0.9 to 1.8 J / g·K.

[0104] The vehicle heat generating part mounting member of this embodiment preferably has a thermal conductivity of 0.1 W / mK or more, more preferably 0.2 W / mK or more, and even more preferably 0.3 W / mK or more.

[0105] Moreover, the vehicle heat generating part mounting member of this embodiment preferably has a thermal conductivity of 12 W / mK or less, more preferably 8 W / mK or less, and even more preferably 4 W / mK or less.

[0106] When the thermal conductivity of the vehicle heat generating portion mounting member of this embodiment is equal to or higher than the above-mentioned preferable lower limit, the heat dissipation property is further improved. If the thermal conductivity of the vehicle heat generating part mounting member of this embodiment is equal to or lower than the above-mentioned preferable upper limit value, deterioration of the resin constituting the brake rotor bell 1 can be further suppressed.

[0107] For example, the thermal conductivity of the vehicle heat generating part mounting member of this embodiment is preferably 0.1 to 12 W / mK or less, more preferably 0.2 to 8 W / mK, and even more preferably 0.3 to 4 W / mK.

[0108] The vehicle heat generating part mounting member of this embodiment preferably has a specific heat at 23°C of 0.4 to 2.0 J / g·K and a thermal conductivity of 0.1 to 12 W / mK, more preferably has a specific heat at 23°C of 0.6 to 1.6 J / g·K and a thermal conductivity of 0.2 to 8 W / mK, and even more preferably has a specific heat at 23°C of 0.8 to 1.2 J / g·K and a thermal conductivity of 0.3 to 4 W / mK.

[0109] The vehicle heat generating part mounting member of this embodiment preferably has a specific heat at 150°C of 0.4 to 2.5 J / g·K and a thermal conductivity of 0.1 to 12 W / mK, more preferably has a specific heat at 150°C of 0.6 to 2.2 J / g·K and a thermal conductivity of 0.2 to 8 W / mK, and even more preferably has a specific heat at 150°C of 0.8 to 1.8 J / g·K and a thermal conductivity of 0.3 to 4 W / mK.

[0110] The vehicle heat generating part mounting member of this embodiment preferably has a primary resonance frequency of 260 Hz or more, more preferably 280 Hz or more, and even more preferably 300 Hz or more.

[0111] The vehicle heat generating part mounting member of this embodiment preferably has a primary resonance frequency of 700 Hz or less, more preferably 600 Hz or less, and even more preferably 500 Hz or less.

[0112] For example, the primary resonance frequency of the vehicle heat generating part mounting member of this embodiment is preferably 260 Hz or more and 700 Hz or less, more preferably 280 Hz or more and 600 Hz or less, and even more preferably 300 Hz or more and 500 Hz or less.

[0113] The vehicle heat generating part mounting component of this embodiment preferably has an emissivity of 0.75 or more, more preferably 0.80 or more, even more preferably 0.85 or more, particularly preferably 0.90 or more, and most preferably 0.95 or more. The upper limit of the emissivity of the vehicle heat generating part mounting part of this embodiment is not particularly limited, but since the emissivity of an ideal black body (an ideal object that absorbs 100% of infrared rays and emits 100% of infrared rays) is 1, the upper limit of the emissivity of the vehicle heat generating part mounting part of this embodiment is less than 1. In other words, the vehicle heat generating part mounting member of this embodiment preferably has an emissivity of 0.75 or more and less than 1, more preferably 0.80 or more and less than 1, even more preferably 0.85 or more and less than 1, particularly preferably 0.90 or more and less than 1, and most preferably 0.95 or more and less than 1.

[0114] If the emissivity of the vehicle heat generating part mounting member of this embodiment is equal to or higher than the above-mentioned preferable lower limit, the heat dissipation performance is further improved.

[0115] Other vehicle heat generating part mounting members can also be manufactured using a method similar to the above-mentioned method for manufacturing the brake rotor bell 1. Note that the manufacturing method for other vehicle heat generating part mounting members also preferably includes a step of obtaining resin pellets containing a thermoplastic resin and a fibrous inorganic filler, and a step of injection molding the resin pellets to obtain the vehicle heat generating part mounting member.

[0116] ≪Resin composition≫ The brake rotor bell 1 of the first embodiment and the vehicle heat generating part mounting members of the other embodiments are injection molded products, and the molding material is a resin composition containing a thermoplastic resin and a fibrous inorganic filler.

[0117] ·Thermoplastic resin Specific examples of thermoplastic resins include polyolefin resins such as polyethylene, polypropylene, polybutadiene, and polymethylpentene; vinyl resins such as vinyl chloride, vinylidene chloride vinyl acetate, and polyvinyl alcohol; polystyrene resins such as acrylonitrile-styrene resin (AS resin) and acrylonitrile-butadiene-styrene resin (ABS resin); polyamide 6 (nylon 6), polyamide 66 (nylon 66), polyamide 11 (nylon 11), polyamide 12 (nylon 12), polyamide 46 (nylon 46), polyamide 610 (nylon 610), polytetramethylene terephthalamide (nylon 4T), polyhexamethylene terephthalamide (nylon 6T), polymetaxylylene adipamide (nylon MXD6), polynonamethylene terephthalamide (nylon 6T), polytetram ... Examples of the polyamide-based resins include poly(ethylene terephthalate) (nylon 9T) and polydecamethylene terephthalamide (nylon 10T); polyester-based resins such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, and polytrimethylene terephthalate; polysulfone-based resins such as modified polysulfone, polyethersulfone, polysulfone, and polyphenylsulfone; polyphenylene sulfides such as linear polyphenylene sulfide, crosslinked polyphenylene sulfide, and semi-crosslinked polyphenylene sulfide, polyether ketones such as polyether ketone, polyether ether ketone, and polyether ketone ketone; polycarbonate; polyphenylene ether; and polyimide-based resins such as thermoplastic polyimide, polyamide imide, and polyether imide.

[0118] As the thermoplastic resin in this embodiment, among the above, liquid crystal polyester or polyethersulfone is preferred from the viewpoint of the impact strength of an injection molded article produced using the resin composition, and liquid crystal polyester is more preferred from the viewpoints of fluidity, heat resistance and dimensional accuracy.

[0119] Liquid crystal polyester The liquid crystal polyester is not particularly limited as long as it is a polyester resin that exhibits liquid crystallinity in a molten state, but it is preferable that the liquid crystal polyester melts at a temperature of 400° C. or less. The liquid crystal polyester in this embodiment may be liquid crystal polyester amide, liquid crystal polyester ether, liquid crystal polyester carbonate, liquid crystal polyester imide, or the like. The liquid crystal polyester in the present embodiment is preferably a wholly aromatic liquid crystal polyester obtained by using only aromatic compounds as raw material monomers.

[0120] Typical examples of the liquid crystal polyester in this embodiment include those obtained by polymerizing (polycondensing) an aromatic hydroxycarboxylic acid, an aromatic dicarboxylic acid, and at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine; those obtained by polymerizing a plurality of aromatic hydroxycarboxylic acids; those obtained by polymerizing an aromatic dicarboxylic acid and at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine; and those obtained by polymerizing a polyester such as polyethylene terephthalate and an aromatic hydroxycarboxylic acid. Here, the aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic hydroxyamine and aromatic diamine may each independently be replaced in part or in whole by a polymerizable derivative thereof.

[0121] Examples of polymerizable derivatives of compounds having a carboxyl group, such as aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids, include those obtained by converting a carboxyl group to an alkoxycarbonyl group or an aryloxycarbonyl group (esters); those obtained by converting a carboxyl group to a haloformyl group (acid halides); and those obtained by converting a carboxyl group to an acyloxycarbonyl group (acid anhydrides).

[0122] Examples of polymerizable derivatives of compounds having a hydroxyl group, such as aromatic hydroxycarboxylic acids, aromatic diols, and aromatic hydroxyamines, include those obtained by acylation of a hydroxyl group to an acyloxyl group (acylated products). Examples of polymerizable derivatives of compounds having an amino group, such as aromatic hydroxyamines and aromatic diamines, include those obtained by acylation of an amino group to convert it into an acylamino group (acylated product).

[0123] The liquid crystal polyester in this embodiment preferably has a repeating unit represented by the following formula (L1) (hereinafter also referred to as "repeating unit (L1)"), and more preferably has a repeating unit (L1), a repeating unit represented by the following formula (L2) (hereinafter also referred to as "repeating unit (L2)"), and a repeating unit represented by the following formula (L3) (hereinafter also referred to as "repeating unit (L3)").

[0124] (L1)-O-Ar 1 -CO- (L2)-CO-Ar 2 -CO- (L3)-X-Ar 3 -Y- [In the formula, Ar 1 represents a phenylene group, a naphthylene group or a biphenylylene group. 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (L4). X and Y each independently represent an oxygen atom or an imino group (-NH-). Ar 1 , Ar 2 or Ar 3 Each hydrogen atom in the group represented by the formula (I) may be independently substituted with a halogen atom, an alkyl group, or an aryl group.

[0125] (L4)-Ar 4 -Z-Ar 5 - [In the formula, Ar 4 and Ar 5each independently represents a phenylene group or a naphthylene group; Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylidene group.

[0126] Ar 1 , Ar 2 or Ar 3 Examples of the halogen atom which can replace one or more hydrogen atoms in the above group represented by the following formula include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0127] Ar 1 , Ar 2 or Ar 3 Examples of the alkyl group which can substitute one or more hydrogen atoms in the group represented by the formula (I) include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group, and the number of carbon atoms is preferably 1 to 10.

[0128] Ar 1 , Ar 2 or Ar 3 Examples of the aryl group which can replace one or more hydrogen atoms in the above group represented by the formula (I) include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group, and the number of carbon atoms is preferably 6 to 20.

[0129] Ar 1 , Ar 2 or Ar 3 When a hydrogen atom in the group represented by the formula: is substituted with the above-mentioned group, the number of substitutions is preferably 1 or 2, and more preferably 1.

[0130] Examples of the alkylidene group for Z in the formula (L4) include a methylene group, an ethylidene group, an isopropylidene group, an n-butylidene group, and a 2-ethylhexylidene group, and the number of carbon atoms therein is preferably 1 to 10.

[0131] The repeating unit (L1) is a repeating unit derived from a specific aromatic hydroxycarboxylic acid. 1 is a 1,4-phenylene group (a repeating unit derived from p-hydroxybenzoic acid), and Ar 1 is a 2,6-naphthylene group (a repeating unit derived from 6-hydroxy-2-naphthoic acid).

[0132] In this specification, the term "derived from" means that the chemical structure of the functional group that contributes to the polymerization is changed due to the polymerization of the raw material monomer, and no other structural changes are caused.

[0133] The repeating unit (L2) is a repeating unit derived from a specific aromatic dicarboxylic acid. 2 is a 1,4-phenylene group (a repeating unit derived from terephthalic acid), Ar 2 is a 1,3-phenylene group (a repeating unit derived from isophthalic acid), Ar 2 is a 2,6-naphthylene group (a repeating unit derived from 2,6-naphthalenedicarboxylic acid), and Ar 2 is a diphenylether-4,4'-diyl group (a repeating unit derived from diphenylether-4,4'-dicarboxylic acid).

[0134] The repeating unit (L3) is a repeating unit derived from a specific aromatic diol, aromatic hydroxylamine or aromatic diamine. The repeating unit (L3) is, for example, Ar 3 is a 1,4-phenylene group (repeating units derived from hydroquinone, p-aminophenol or p-phenylenediamine), and Ar 3 is a 4,4'-biphenylylene group (a repeating unit derived from 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl).

[0135] The content of the repeating unit (L1) is preferably 30 mol % or more, more preferably 30 mol % to 80 mol %, even more preferably 40 mol % to 70 mol %, and particularly preferably 45 mol % to 65 mol %, based on the total amount of all repeating units (the mass of each repeating unit constituting the liquid crystal polyester is divided by the formula weight of each repeating unit to determine the substance amount equivalent (mol) of each repeating unit, and the total value).

[0136] The content of the repeating unit (L2) is preferably 35 mol% or less, more preferably 10 mol% or more and 35 mol% or less, even more preferably 15 mol% or more and 30 mol% or less, and particularly preferably 17.5 mol% or more and 27.5 mol% or less, based on the total amount of all repeating units.

[0137] The content of the repeating unit (L3) is preferably 35 mol% or less, more preferably 10 mol% or more and 35 mol% or less, even more preferably 15 mol% or more and 30 mol% or less, and particularly preferably 17.5 mol% or more and 27.5 mol% or less, based on the total amount of all repeating units.

[0138] The higher the content of the repeating unit (L1), the more likely it is that the melt fluidity, heat resistance, strength, and rigidity will improve. However, if the content is too high, the melt temperature and melt viscosity will tend to increase, and the temperature required for molding will tend to become higher.

[0139] The ratio of the content of the repeating unit (L2) to the content of the repeating unit (L3), expressed as [content of the repeating unit (L2)] / [content of the repeating unit (L3)] (mol / mol), is preferably 0.9 / 1 to 1 / 0.9, more preferably 0.95 / 1 to 1 / 0.95, and even more preferably 0.98 / 1 to 1 / 0.98.

[0140] The liquid crystal polyester in the present embodiment may have two or more kinds of repeating units (L1) to (L3) independently. The liquid crystal polyester may have a repeating unit other than the repeating units (L1) to (L3), and the content of the repeating unit other than the repeating units (L1) to (L3) is preferably 10 mol % or less, more preferably 5 mol % or less, based on the total amount of all repeating units.

[0141] The liquid crystal polyester in the present embodiment preferably has a repeating unit (L3) in which X and Y are each an oxygen atom, i.e., a repeating unit derived from a specific aromatic diol, since the melt viscosity is likely to be low. It is more preferable that the liquid crystal polyester has only a repeating unit (L3) in which X and Y are each an oxygen atom.

[0142] The liquid crystal polyester in this embodiment is preferably produced by melt-polymerizing raw material monomers corresponding to the repeating units constituting the polyester, and then solid-phase polymerizing the resulting polymer. This allows the production of a high molecular weight liquid crystal polyester with high heat resistance, strength, and rigidity with good operability. The melt polymerization may be carried out in the presence of a catalyst, examples of which include metal compounds such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, and antimony trioxide, and nitrogen-containing heterocyclic compounds such as 4-(dimethylamino)pyridine and 1-methylimidazole, with the nitrogen-containing heterocyclic compounds being preferred.

[0143] Polyethersulfone Polyethersulfone is typically a resin having a repeating unit containing a divalent aromatic group (a residue formed by removing two hydrogen atoms bonded to an aromatic ring from an aromatic compound), a sulfonyl group (-SO2-), and an oxygen atom. From the viewpoint of heat resistance and chemical resistance, polyethersulfone preferably has a repeating unit represented by the following formula (S1) (hereinafter, sometimes referred to as "repeat unit (S1)"), and may further have one or more other repeating units such as a repeating unit represented by the following formula (S2) (hereinafter, sometimes referred to as "repeat unit (S2)") or a repeating unit represented by the following formula (S3) (hereinafter, sometimes referred to as "repeat unit (S3)").

[0144] (S1)-Ph 1 -SO2-Ph 2 -O-

[0145] Ph1 and Ph 2 each independently represents a phenylene group. A hydrogen atom in the phenylene group may each independently be substituted with an alkyl group, an aryl group or a halogen atom.

[0146] (S2)-Ph 3 -R-Ph 4 -O-

[0147] Ph 3 and Ph 4 each independently represents a phenylene group. A hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group, or a halogen atom. R represents an alkylidene group, an oxygen atom, or a sulfur atom.

[0148] (S3)-(Ph 5 ) n -O-

[0149] Ph 5 represents a phenylene group. Each hydrogen atom in the phenylene group may be independently substituted with an alkyl group, an aryl group or a halogen atom. n represents an integer of 1 to 3. When n is 2 or more, a plurality of Ph 5 may be the same or different from each other.

[0150] Ph 1 ~Ph 5 The phenylene group represented by any one of the following formulas may be a p-phenylene group, an m-phenylene group, or an o-phenylene group, but is preferably a p-phenylene group.

[0151] Examples of the alkyl group which may substitute a hydrogen atom in the phenylene group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group and an n-decyl group, and the number of carbon atoms therein is, for example, 1 to 10.

[0152] Examples of the aryl group which may replace a hydrogen atom in the phenylene group include a phenyl group, an o-tolyl group, a m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group, and the number of carbon atoms is, for example, 6 to 20. When a hydrogen atom in the phenylene group is replaced by these groups, the number is, for example, 2 or less, and preferably 1 or less, independently for each phenylene group.

[0153] Examples of the alkylidene group represented by R include a methylene group, an ethylidene group, an isopropylidene group, and a 1-butylidene group, and the number of carbon atoms thereof is, for example, 1 to 5.

[0154] The polyethersulfone preferably contains 50 mol % or more of the repeating unit (S1) based on the total of all repeating units, more preferably 80 mol % or more, and further preferably contains substantially only the repeating unit (S1). The polyethersulfone may contain two or more types of repeating units (S1) to (S3) independently.

[0155] Polyethersulfone can be produced by polycondensing a dihalogenosulfone compound and a dihydroxy compound that correspond to the repeating units constituting the polyethersulfone.

[0156] For example, a resin having a repeating unit (S1) can be produced by using a compound represented by the following formula (S4) (hereinafter sometimes referred to as "compound (S4)") as a dihalogenosulfone compound and a compound represented by the following formula (S5) as a dihydroxy compound.

[0157] In addition, a resin having the repeating unit (S1) and the repeating unit (S2) can be produced by using the compound (S4) as the dihalogenosulfone compound and the compound represented by the following formula (S6) as the dihydroxy compound.

[0158] In addition, a resin having the repeating unit (S1) and the repeating unit (S3) can be produced by using the compound (S4) as the dihalogenosulfone compound and the compound represented by the following formula (S7) as the dihydroxy compound.

[0159] (S4)X 1 -Ph 1 -SO2-Ph 2 -X 2

[0160] X 1 and X 2 Each independently represents a halogen atom. 1 and Ph 2 has the same meaning as above.

[0161] (S5)HO-Ph 1 -SO2-Ph 2 -OH

[0162] Ph 1 and Ph 2 has the same meaning as above.

[0163] (S6)HO-Ph 3 -R-Ph 4 -OH

[0164] Ph 3 , Ph 4 and R has the same meaning as above.

[0165] (S7)HO-(Ph 5 ) n -OH

[0166] Ph 5 and n are as defined above.

[0167] The polycondensation is preferably carried out in a solvent using an alkali metal salt of carbonate. The alkali metal salt of carbonate may be an alkali carbonate, which is a normal salt, an alkali bicarbonate (alkali hydrogen carbonate), which is an acid salt, or a mixture of both.

[0168] As the alkali carbonate, sodium carbonate or potassium carbonate is preferably used. As the alkali bicarbonate, sodium bicarbonate or potassium bicarbonate is preferably used.

[0169] As the solvent, organic polar solvents such as dimethyl sulfoxide, 1-methyl-2-pyrrolidone, sulfolane (1,1-dioxothiane), 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, dimethyl sulfone, diethyl sulfone, diisopropyl sulfone, and diphenyl sulfone are preferably used.

[0170] The reduced viscosity of polyethersulfone is, for example, 0.3 dL / g or more, preferably 0.33 dL / g or more and 0.45 dL / g or less, more preferably 0.36 dL / g or more and 0.41 dL / g or less. If the reduced viscosity is 0.3 dL / g or more, heat resistance, strength, and rigidity are easily improved. On the other hand, if the reduced viscosity is 0.45 dL / g or less, the molding temperature and melt viscosity do not become too high, and it is easy to mold into a predetermined shape.

[0171] In the polycondensation, if no side reaction occurs, the closer the molar ratio of the dihalogenosulfone compound to the dihydroxy compound is to 1:1, the greater the amount of the alkali metal salt of carbonate used, the higher the polycondensation temperature, and the longer the polycondensation time, the higher the degree of polymerization of the resulting polyethersulfone and the higher the reduced viscosity. However, in reality, side reactions such as substitution reaction of halogeno groups with hydroxyl groups and depolymerization occur due to the by-product alkali hydroxide, and this side reaction tends to reduce the degree of polymerization of the resulting polyethersulfone and the reduced viscosity. Therefore, it is preferable to adjust the molar ratio of the dihalogenosulfone compound to the dihydroxy compound, the amount of the alkali metal salt of carbonate used, the polycondensation temperature, and the polycondensation time so as to obtain a polyethersulfone having a desired reduced viscosity, taking into consideration the degree of this side reaction.

[0172] The thermoplastic resin in the present embodiment may be used alone or in combination of two or more kinds.

[0173] - Fibrous inorganic filler Examples of fibrous inorganic fillers include glass fibers; carbon fibers such as PAN-based, pitch-based, rayon-based, phenol-based, and lignin-based carbon fibers; ceramic fibers such as silica fibers, alumina fibers, and silica-alumina fibers; metal fibers such as iron, gold, copper, aluminum, brass, and stainless steel; silicon carbide fibers; and boron fibers. Further, examples of the fibrous inorganic filler include whiskers such as potassium titanate whiskers, barium titanate whiskers, wollastonite whiskers, aluminum borate whiskers, silicon nitride whiskers, and silicon carbide whiskers.

[0174] The length-weighted average fiber length of the fibrous inorganic filler in the injection molded product in this embodiment is preferably 100 μm or more, more preferably 120 μm or more, even more preferably 130 μm or more, particularly preferably 135 μm or more, and most preferably 140 μm or more. In addition, the length-weighted average fiber length of the fibrous inorganic filler in the injection-molded product in this embodiment is preferably less than 5 mm, more preferably 2 mm or less, even more preferably 1 mm or less, particularly preferably 500 μm or less, and most preferably 300 μm or less.

[0175] The fibrous inorganic filler in the injection molded product in this embodiment preferably has a length-weighted average fiber length of 100 μm or more and less than 5 mm, more preferably 120 μm or more and 2 mm or less, even more preferably 130 μm or more and 1 mm or less, particularly preferably 135 μm or more and 500 μm or less, and most preferably 140 μm or more and 300 μm or less.

[0176] When the length-weighted average fiber length of the fibrous inorganic filler in the injection molded article is equal to or greater than the lower limit of the above-mentioned preferred range, strength and heat dissipation properties are further improved, whereas when the length-weighted average fiber length is equal to or less than the upper limit of the above-mentioned preferred range, molding is further facilitated.

[0177] The injection molded article in this embodiment may be an injection molded article manufactured using resin pellets obtained by the resin pellet manufacturing method described later. The resin pellets are manufactured so that the fibrous inorganic filler is arranged approximately parallel to the longitudinal direction of the resin pellets and the length of the fibrous inorganic filler is substantially the same as the length of the resin pellets. In this case, the length-weighted average fiber length of the fibrous inorganic filler in the injection molded article is preferably 0.3 mm or more, more preferably 1 mm or more, and even more preferably 1.5 mm or more. In such a case, the fibrous inorganic filler in the injection molded article preferably has a length-weighted average fiber length of 10 mm or less, more preferably 5 mm or less, and even more preferably 3 mm or less.

[0178] In such a case, the fibrous inorganic filler in the injection molded article preferably has a length-weighted average fiber length of 0.3 mm or more and 10 mm or less, more preferably 1 mm or more and 5 mm or less, and even more preferably 1.5 mm or more and 3 mm or less.

[0179] In such a case, when the length-weighted average fiber length of the fibrous inorganic filler in the injection molded article is equal to or greater than the lower limit of the above-mentioned preferred range, strength and heat dissipation properties are further improved, whereas when the length is equal to or less than the upper limit of the above-mentioned preferred range, molding is further facilitated.

[0180] In this embodiment, the fiber length and length-weighted average fiber length of the fibrous inorganic filler in the injection molded product are measured by the following procedure. Step (1): 2 g of the injection molded product is heated in a muffle furnace to remove the resin content (thermoplastic resin). For example, when the fibrous inorganic filler is carbon fiber, the heating conditions are 500° C. and 3 hours. When the fibrous inorganic filler is glass fiber, the heating conditions are 600° C. and 4 hours.

[0181] Step (2) After removing the resin, the fibrous inorganic filler obtained is dispersed in 1000 mL of an aqueous solution containing 0.05% by volume of a surfactant (Micro90, manufactured by INTERNATIONAL PRODUCTS CORPORATION) to prepare a dispersion.

[0182] Step (3): Take 100 mL from the dispersion and dilute it with pure water 5 to 20 times. Take a portion of the diluted dispersion and observe the fibrous inorganic filler with a microscope (VH-Z25, Keyence, magnification 10 to 20 times; VHZ-ST, Keyence, magnification 100 times), and take 10 images for each sample without overlapping the photographed areas. However, if the fibrous inorganic filler is carbon fiber, take 50 mL from the diluted dispersion and filter it under reduced pressure using a φ90 mm Kiriyama funnel filter paper (No. 5C), and take an image of the carbon fiber dispersed on the filter paper. When the fibrous inorganic filler is glass fiber, 50 mL is taken out of the diluted dispersion liquid and dispersed in a petri dish, and then an image of the glass fiber dispersed in the petri dish is taken.

[0183] Step (4): Measure the length of all fibrous inorganic fillers present in one captured image using the measuring tool of the microscope. Note that bent fibrous inorganic fillers are measured by multipoint measurement, and fibrous inorganic fillers that are in contact with the edge of the image are not measured. Repeat the same procedure for the 10 captured images in turn to measure the fiber length of the fibrous inorganic filler until the total number of fibers measured in the 10 captured images exceeds 500. If the total number of fibers in the 10 captured images does not exceed 500, return to step (3), adjust the dilution ratio with pure water as appropriate, retake the image, and remeasure the fiber length.

[0184] Step (5) From the fiber lengths of the fibrous inorganic filler measured in step (4), the length-weighted average fiber length lm = (Σli 2Calculate (Σni>500) / (Σli×ni). li: fiber length of fibrous inorganic filler ni: number of fibrous inorganic fillers with fiber length li

[0185] In addition, when there are few bent fibrous inorganic fillers, in the above step (4), five images of the fibrous inorganic filler in the above step (3) may be photographed, and all five images taken may be binarized using image processing software (WinROOF2018, manufactured by Mitani Shoji Co., Ltd.) to measure the fiber length of the fibrous inorganic filler. In this case, the fiber length is measured as follows.

[0186] (a) The captured image is subjected to monochrome pixelation processing. (b) A binarization process is performed so that only the photographed fibrous inorganic filler is colored. (c) Fiber length is measured using the needle separation function of the image processing software. (d) The fiber lengths of fibrous inorganic fillers that could not be binarized in (c) and curved fibrous inorganic fillers are measured by multi-point measurement. However, in (c) and (d), fibrous inorganic fillers of 10 μm or less are judged as noise when the magnification is 100 times, and fibrous inorganic fillers of 50 μm or less are judged as noise when the magnification is 10 to 20 times, and are not included in the number of fibrous inorganic fillers measured, n. If the number of fibrous inorganic fillers measured, n, does not exceed 500, return to step (3) and take additional images and measure until n exceeds 500.

[0187] The fineness of the fibrous inorganic filler in the injection molded product in this embodiment is not particularly limited, but is preferably 200 g / 1000 m or more, more preferably 500 g / 1000 m or more, and even more preferably 800 g / 1000 m or more. The fineness of the fibrous inorganic filler is preferably 3750 g / 1000 m or less, more preferably 3200 g / 1000 m or less, and even more preferably 2500 g / 1000 m or less.

[0188] For example, the fineness of the fibrous inorganic filler in the injection molded product is preferably 200 g / 1000 m or more and 3750 g / 1000 m or less, and more preferably 800 g / 1000 m or more and 2500 g / 1000 m or less.

[0189] In this specification, the term "fineness" refers to the thickness of a bundle of fibrous inorganic fillers aligned in one direction (thickness of the fiber bundle).

[0190] The number average fiber diameter of the fibrous inorganic filler in the injection molded article is not particularly limited, but is preferably from 1 to 40 μm, and more preferably from 3 to 35 μm.

[0191] When the fibrous inorganic filler is carbon fiber, the number average fiber diameter of the carbon fiber is preferably 1 μm to 40 μm, preferably 3 μm to 35 μm, preferably 1 μm to 25 μm, more preferably 3 μm to 20 μm, and even more preferably 5 μm to 15 μm.

[0192] When the fibrous inorganic filler is glass fiber, the number average fiber diameter of the glass fiber is preferably from 5 to 35 μm, more preferably from 10 to 25 μm, and further preferably from 10 to 20 μm.

[0193] The number average fiber diameter of the fibrous inorganic filler in the injection molded product can be measured, for example, by removing the resin content in a manner similar to that of step (1) for measuring the fiber length and length-weighted average fiber length of the fibrous inorganic filler described above, observing the obtained fibrous inorganic filler under a scanning electron microscope (1000x), and measuring the fiber diameters of 500 randomly selected fibrous inorganic fillers, and then using the number average value of the measured values. When the number average fiber diameter of the fibrous inorganic filler is at least the lower limit of the above preferred range, the fibrous inorganic filler is easily dispersed in the injection molded article. On the other hand, when the content is equal to or less than the upper limit of the above preferred range, the fibrous inorganic filler efficiently reinforces the injection-molded article, thereby making it possible to further improve the strength of the injection-molded article.

[0194] Among the above, the fibrous inorganic filler in this embodiment is preferably carbon fiber from the viewpoint of further improving mechanical strength and heat dissipation properties.

[0195] As the carbon fiber, PAN-based, pitch-based, rayon-based, phenol-based, and lignin-based carbon fibers are preferred, and from the viewpoint of the mechanical properties of the resulting molded product, PAN-based carbon fiber or pitch-based carbon fiber is more preferred, and pitch-based carbon fiber is even more preferred because it can achieve a particularly high elastic modulus. For the purpose of imparting electrical conductivity, carbon fibers coated with a metal such as nickel, copper, or ytterbium can also be preferably used.

[0196] Examples of PAN-based carbon fibers include "TORAYCA (registered trademark)" manufactured by Toray Industries, Inc., "PYROFIL (registered trademark)" manufactured by Mitsubishi Chemical Corporation, and "Tenax (registered trademark)" manufactured by Teijin Limited.

[0197] The carbon fiber has a tensile strength of preferably 2000 MPa or more, more preferably 2500 MPa or more, and further preferably 3000 MPa or more. By using carbon fibers with high tensile strength, fiber breakage during the processing steps up to the production of injection molded products is reduced, and the fibers can be left in place for a long time, making it easier to achieve the effects of the invention. The upper limit of the tensile strength of the carbon fiber is, for example, 6000 MPa or less. The tensile strength of the carbon fiber means a value measured in accordance with JIS R 7606:2000.

[0198] Pitch-based carbon fibers can be mainly classified into mesophase pitch-based carbon fibers made from mesophase pitch as a starting material and isotropic pitch-based carbon fibers made from isotropic pitch as a starting material. Mesophase pitch-based carbon fibers are preferably used from the viewpoint of obtaining high mechanical properties.

[0199] The pitch-based carbon fiber has a tensile modulus of elasticity of preferably 200 GPa or more, more preferably 250 GPa or more, further preferably 500 GPa or more, and particularly preferably 650 GPa or more. By using highly elastic pitch-based carbon fibers, the elastic modulus of the injection molded product can be improved, making it easier to obtain the effects of the invention. The upper limit of the tensile modulus of the pitch-based carbon fiber is, for example, 2000 GPa or less. The tensile modulus of the pitch-based carbon fiber means a value measured in accordance with JIS R 7606:2000.

[0200] Examples of pitch-based carbon fibers include "DIALEAD (registered trademark)" manufactured by Mitsubishi Chemical Corporation, "GRANOC (registered trademark)" manufactured by Nippon Graphite Fiber Co., Ltd., "DONACARBO (registered trademark)" manufactured by Osaka Gas Chemicals Co., Ltd., and "KUREKA (registered trademark)" manufactured by Kureha Co., Ltd. As mesophase pitch-based carbon fibers, "DIALEAD (registered trademark)" manufactured by Mitsubishi Chemical Corporation and "GRANOC (registered trademark)" manufactured by Nippon Graphite Fiber Co., Ltd. are preferred because they can improve the mechanical properties of molded products.

[0201] In this embodiment, the content of the fibrous inorganic filler in the injection molded product is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 50 parts by mass or more, and even more preferably 75 parts by mass or more, per 100 parts by mass of the thermoplastic resin. The content of the fibrous inorganic filler in the injection molded product in this embodiment is preferably 120 parts by mass or less, and more preferably 100 parts by mass or less, per 100 parts by mass of the thermoplastic resin.

[0202] The content of the fibrous inorganic filler in the injection molded product in this embodiment is, for example, preferably 30 parts by mass or more and 120 parts by mass or less, more preferably 40 parts by mass or more and 100 parts by mass or less, even more preferably 50 parts by mass or more and 100 parts by mass or less, and even more preferably 75 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin.

[0203] When the content of the fibrous inorganic filler in the injection molded article in this embodiment is equal to or greater than the above-mentioned preferable lower limit, the effects of the present invention are easily enhanced. On the other hand, when it is equal to or less than the above-mentioned preferable upper limit, the fibrous inorganic filler is easily dispersed in the injection molded article.

[0204] Other ingredients The resin composition that is the molding material for the brake rotor bell 1 of this embodiment may contain, in addition to the above-mentioned thermoplastic resin and fibrous inorganic filler, one or more other fillers, additives, etc., as necessary.

[0205] Other fillers Other fillers include plate-like fillers and spherical fillers. The other fillers may be inorganic fillers or organic fillers.

[0206] Examples of the plate-like filler include talc, mica, graphite, wollastonite, glass flakes, barium sulfate, and calcium carbonate. The mica may be muscovite, phlogopite, fluorophlogopite, or tetrasilicic mica.

[0207] Particulate fillers include silica, alumina, titanium oxide, glass beads, glass balloons, boron nitride, silicon carbide, and calcium carbonate.

[0208] Examples of fibrous organic fillers include polyester fibers, para- and meta-aramid fibers, and PBO fibers.

[0209] Additives Examples of the additives include flame retardants, conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloration inhibitors, heat stabilizers, release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foam control agents, viscosity adjusters, and surfactants.

[0210] -Method of manufacturing resin pellets As described above, the resin composition that is the molding material for the brake rotor bell 1 of the first embodiment and the vehicle heat generating part mounting member of the other embodiments is preferably resin pellets. For example, a manufacturing method for the brake rotor bell 1 of the first embodiment and the vehicle heat generating part mounting members of the other embodiments preferably includes a step of obtaining a resin pellet containing a thermoplastic resin and a fibrous inorganic filler by the method described below, and a step of injection molding the resin pellet to obtain the brake rotor bell 1 of this embodiment.

[0211] In the method for producing resin pellets in this embodiment, for example, a thermoplastic resin and, if necessary, other components are melt-kneaded, and the resulting melt is impregnated into a fibrous inorganic filler and pelletized, thereby obtaining resin pellets.

[0212] FIG. 6 shows an embodiment of a resin pellet manufacturing apparatus. In the present embodiment shown in FIG. 6, a case will be described in which resin pellets 25 are obtained by using a fiber roving 20 obtained by winding up a fiber bundle 21 in the form of a roll in which a plurality of fibrous inorganic fillers are bundled with a sizing agent.

[0213] 6, the manufacturing apparatus 200 includes a preheating section 221, an impregnation section 223, a cooling section 225, a take-up section 227, a cutting section 229, and transport rolls 201 to 209. In the manufacturing apparatus 200 shown in FIG. 6, an extruder 220 is connected to the impregnation section 223.

[0214] 6 shows a state in which the fiber bundle 21 is continuously unwound from the fiber roving 20. In this embodiment, the fiber bundle 21 unwound from the fiber roving 20 is transported in the longitudinal direction by transport rolls 201-209, while the resin pellets 25 are produced.

[0215] The fineness of the fiber roving 20 used in the production of the resin pellets of this embodiment is 500 g / 1000 m or more and 3400 g / 1000 m or less, preferably 800 g / 1000 m or more and 3200 g / 1000 m or less, and more preferably 800 g / 1000 m or more and 2400 g / 1000 m or less. When the fineness of the fiber roving 20 is equal to or greater than the lower limit of the above-mentioned preferred range, the fiber roving 20 is easy to handle in the method for producing resin pellets. When the fineness of the fiber roving 20 is equal to or less than the upper limit of the above-mentioned preferred range, the fibers are easily dispersed in the thermoplastic resin, and the fibers are easy to handle when producing resin pellets.

[0216] The number average fiber diameter of the fiber roving 20 is preferably 5 to 35 μm, more preferably 10 to 25 μm, and further preferably 10 to 20 μm.

[0217] The number average fiber diameter of the fiber roving 20 is determined by observing the fibrous inorganic filler under a scanning electron microscope (1000x) and measuring the fiber diameters of 500 randomly selected fibrous inorganic fillers, and the number average value is used. When the number average fiber diameter of the fiber roving 20 is equal to or greater than the lower limit of the above-mentioned preferred range, the fibrous inorganic filler is easily dispersed in the resin pellets. In addition, the fibrous inorganic filler is easy to handle during the production of the resin pellets. On the other hand, when the number average fiber diameter is equal to or less than the upper limit of the above-mentioned preferred range, the reinforcement of the injection molded product by the fibrous inorganic filler is efficiently performed. Therefore, the strength of the injection molded product can be improved.

[0218] In this embodiment, the fiber roving 20 used is one that has been treated with a sizing agent. A fibrous inorganic filler that has been appropriately sized has superior productivity and quality stability during pellet production, and can reduce the variation in physical properties of injection-molded products.

[0219] The sizing agent is not particularly limited, but examples thereof include nylon polymers, polyether polymers, epoxy polymers, ester polymers, urethane polymers, mixed polymers thereof, and modified polymers thereof. Also usable are known coupling agents such as so-called silane coupling agents such as aminosilane and epoxysilane, and titanium coupling agents.

[0220] The fibrous inorganic filler used in the resin pellets of this embodiment does not necessarily need to have single fibers aligned in one direction, but from the viewpoint of productivity in the process of producing the molding material, it is preferable that the single fibers are aligned in one direction and the fiber bundles are continuous along the length of the fibers.

[0221] From the viewpoint of economic efficiency and improved impregnation, the number of single yarns of the fiber roving 20 is preferably 1,000 to 10,000, more preferably 1,000 to 8,000, and even more preferably 1,500 to 6,000.

[0222] In the pre-heating section 221, the fiber bundle 21 unwound from the fiber roving 20 is heated and dried. The heating temperature is not particularly limited, but is, for example, 50 to 250° C. The heating time in the pre-heating section 221 is not particularly limited, but is, for example, 3 to 30 seconds.

[0223] In the impregnation section 223, the fiber bundles 21 are impregnated with a molding material M (thermoplastic resin, and other components blended as necessary) other than the fiber bundles 21. The thermoplastic resin is appropriately selected taking into consideration the type, melt viscosity, flow initiation temperature, etc. of the second thermoplastic resin, as described below. The thermoplastic resins may be used alone or in combination of two or more.

[0224] The molding material M may be fed through the supply port 223a and heated in the impregnation section 223 to obtain a molten material, which is then impregnated into the fiber bundle 21. Alternatively, the molding material M melt-kneaded in the extruder 220 may be fed through the supply port 223a to impregnate the fiber bundle 21. In the embodiment shown in FIG. 6, a resin structure 23 is obtained in which the fiber bundle 21 is impregnated with and coated with the molten material.

[0225] The heating temperature in the impregnation section 223 is appropriately determined depending on the type of thermoplastic resin, and is preferably set to a temperature 10 to 80°C higher than the flow start temperature of the thermoplastic resin used, for example 300 to 400°C.

[0226] In the impregnation section 223, 100 parts by mass of thermoplastic resin is impregnated into preferably 30 to 120 parts by mass of fibrous inorganic filler (fiber bundles 21), more preferably 50 to 100 parts by mass of fibrous inorganic filler, and even more preferably 75 to 100 parts by mass of fibrous inorganic filler, depending on the characteristics required of the injection-molded product. When the amount of the fibrous inorganic filler is equal to or more than the lower limit of the above-mentioned preferred range, the strength of the injection-molded product is further improved, whereas when the amount is equal to or less than the upper limit of the above-mentioned preferred range, the fiber bundles are easily opened and the fiber bundles are easily impregnated with the thermoplastic resin. By changing the nozzle diameter of the die head at the outlet of the impregnation section 223 relative to the diameter of the fiber bundle 21, the compounding ratio of the thermoplastic resin to the fibrous inorganic filler in the resin structure 23 can be adjusted.

[0227] In the cooling section 225, the resin structure 23 (resin structure 23 in which the fiber bundle is impregnated with and coated with the molten material) heated in the impregnation section 223 is cooled to, for example, 50 to 150° C. The cooling time is not particularly limited, but is, for example, 3 to 30 seconds.

[0228] In the take-up section 227 , the resin structure 23 cooled in the cooling section 225 is continuously taken up and sent to the next cutting section 229 .

[0229] In the cutting unit 229, the cooled resin structure 23 is cut to a desired length to produce resin pellets 25. The cutting unit 229 includes, for example, a rotary blade.

[0230] Using the above-described manufacturing apparatus 200, the resin pellets of this embodiment, for example, pellets in which fibrous inorganic filler is solidified with a thermoplastic resin, are manufactured as follows.

[0231] Steps for obtaining a resin structure: While continuously paying out a fiber bundle 21 in which a plurality of single fibers are bundled with a sizing agent from a fiber roving 20, the fiber bundle 21 is first heated and dried in a pre-heating section 221. Next, while the dried fiber bundle 21 is being supplied to the impregnation section 223, the molding material M melt-kneaded by the extruder 220 is fed from the supply port 223a to impregnate the fiber bundle 21 with the molten molding material M. This results in a resin structure 23 in which the fiber bundle is impregnated and coated with the molten material. Thereafter, the resin structure 23 heated in the impregnation section 223 is cooled in the cooling section 225. In the resin structure 23 thus obtained, the fibers are arranged approximately parallel to the longitudinal direction of the resin structure 23 . "The fibers are arranged approximately parallel to the longitudinal direction of the resin structure" means that the angle between the longitudinal direction of the fibers and the longitudinal direction of the resin structure is approximately 0°, and specifically, the angle between the longitudinal directions of the fibers and the resin structure is -5° to 5°.

[0232] Process for obtaining pellets: Next, the cooled resin structure 23 is taken up in a strand shape by a take-up unit 227 and fed to a cutting unit 229 . Next, in a cutting section 229 , the strand-like resin structure 23 is cut in its longitudinal direction to a predetermined length, thereby obtaining resin pellets 25 . The predetermined length of the resin pellet 25 here means the length of the resin pellet 25 that is set according to the required performance of an injection-molded product made of the resin pellet 25. In the resin pellet obtained by the manufacturing method of this embodiment, the length of the resin pellet 25 and the length of the fibers arranged in the resin pellet 25 are substantially the same length. "The length of the pellet and the length of the fiber are substantially the same" means that the length-weighted average fiber length of the fibers arranged in the pellet is 95 to 105% of the length of the pellet in the longitudinal direction.

[0233] In the manner described above, resin pellets (resin pellets 25) containing a thermoplastic resin and a fibrous inorganic filler are produced. The resin pellet 25 is a fibrous inorganic filler solidified with a thermoplastic resin, and the fibrous inorganic filler is arranged approximately parallel to the longitudinal direction of the pellet. The length of the fibrous inorganic filler arranged in the resin pellet 25 is substantially the same as the length of the pellet. The length of the resin pellet 25 produced in this embodiment depends on the required performance of the injection molded product made of the resin pellet 25, and is, for example, 3 to 50 mm.

[0234] In this way, the fibrous inorganic filler is arranged approximately parallel to the longitudinal direction of the pellet, and the length of the fibrous inorganic filler is substantially the same as the length of the pellet, so that when the injection molded article is made, the remaining fibrous inorganic filler in the injection molded article can be made into long fibers, which is effective in improving the strength, heat resistance, and heat dissipation of the injection molded article.

[0235] The orientation direction of the fibrous inorganic filler in the resin pellet can be confirmed by observing a cross section of the resin pellet cut in the longitudinal direction under a microscope. The length of the fibrous inorganic filler in the resin pellet is determined by the same procedure as in the measurement of the fiber length of the fibrous inorganic filler in the injection molded product described above.

[0236] (vehicle) A second aspect of the present invention is a vehicle in which the vehicle heat generating part mounting member according to the first aspect described above is mounted to a heat generating part.

[0237] Examples of vehicles include bicycles, motorcycles, automobiles, and trains. Of the above, the vehicle of this embodiment is preferably a four-wheeled automobile in which the vehicle heat generating part mounting part relating to the first aspect described above is mounted to the heat generating part, from the viewpoint of further improving fuel efficiency by reducing the weight of the parts.

[0238] In the vehicle of this embodiment, the mounting member attached to the heat generating part is the vehicle heat generating part mounting member according to the first aspect described above, so that the vehicle is lighter in weight than a vehicle in which a conventional metal mounting member is attached to the heat generating part. In addition, when the primary resonance frequency of the vehicle heat generating part mounting member according to the first aspect described above is 260 Hz or more, the noise inside the vehicle is also further reduced. EXAMPLES

[0239] The present invention will be described in more detail below with reference to specific examples, although the present invention is not limited to the following examples.

[0240] [Thermoplastic resin flow start temperature] The flow starting temperature of the thermoplastic resin described below was evaluated using a flow tester (Shimadzu Corporation, CFT-500 model). Specifically, about 2 g of the thermoplastic resin was filled into a capillary rheometer equipped with a die with an inner diameter of 1 mm and a length of 10 mm. The filled thermoplastic resin was then extruded from the nozzle of the rheometer at a heating rate of 4°C / min under a load of 9.8 MPa (100 kg / cm2), and the temperature at which the melt viscosity was 4800 Pa s (48000 poise) was defined as the flow starting temperature.

[0241] <Production of Thermoplastic Resins> <Production of Liquid Crystal Polyester 1 (LCP1)> (1) Melt polymerization Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1034.99 g (5.5 mol) of 6-hydroxy-2-naphthoic acid, 378.33 g (1.75 mol) of 2,6-naphthalenedicarboxylic acid, 83.07 g (0.5 mol) of terephthalic acid, 272.52 g of hydroquinone (2.475 mol, 0.225 molar excess with respect to the total amount of 2,6-naphthalenedicarboxylic acid and terephthalic acid), 1226.87 g (12 mol) of acetic anhydride, and 0.17 g of 1-methylimidazole as a catalyst were placed, and the gas in the reactor was replaced with nitrogen gas. The mixture was then heated from room temperature to 145° C. over a period of 15 minutes while stirring under a nitrogen gas flow, and refluxed at 145° C. for 1 hour.

[0242] Next, while distilling off the by-product acetic acid and unreacted acetic anhydride, the temperature was raised from 145°C to 310°C over 3.5 hours, and after maintaining at 310°C for 3 hours, the contents were removed and cooled to room temperature. The obtained solid was pulverized in a pulverizer to a particle size of about 0.1 to 1 mm to obtain a prepolymer powder.

[0243] (2) Solid-state polymerization The prepolymer powder was heated in a nitrogen atmosphere from room temperature to 250°C over 1 hour, then heated from 250°C to 310°C over 10 hours, and held at 310°C for 5 hours to carry out solid-state polymerization. After solid-state polymerization, the mixture was cooled to obtain powdered liquid crystal polyester 1 (LCP1). Liquid crystal polyester 1 (LCP1) has the following repeat units: Ar 1 55 mol % of repeating units (L1) each having a 2,6-naphthylene group, 2 17.5 mol % of repeating units (L2) in which the repeating unit is a 2,6-naphthylene group, 2 5 mol % of repeating units (L2) in which R is a 1,4-phenylene group, and Ar 3 The repeating unit (L3) having a 1,4-phenylene group accounts for 22.5 mol %. The flow initiation temperature of liquid crystal polyester 1 (LCP1) was 320°C.

[0244] <Production of Liquid Crystal Polyester 2 (LCP2)> (1) Melt polymerization In a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer and a reflux condenser, 994.5g (7.2 mol) of p-hydroxybenzoic acid, 446.9g (2.4 mol) of 4,4'-dihydroxybiphenyl, 239.2g (1.44 mol) of terephthalic acid, 159.5g (0.96 mol) of isophthalic acid and 1347.6g (13.2 mol) of acetic anhydride were charged, 0.2g of 1-methylimidazole was added, and the inside of the reactor was sufficiently replaced with nitrogen gas. After that, the temperature was raised from room temperature to 150°C over 30 minutes while stirring under a nitrogen gas flow, and refluxed for 1 hour while maintaining the temperature at 150°C. Next, 0.9 g of 1-methylimidazole was added, and the temperature was raised from 150° C. to 320° C. over 2 hours and 50 minutes while distilling off the by-product acetic acid and unreacted acetic anhydride. The reaction was terminated when an increase in torque was observed, yielding a prepolymer.

[0245] (2) Solid-state polymerization The prepolymer thus obtained was cooled to room temperature and crushed in a coarse crusher to obtain a prepolymer powder. The prepolymer powder was heated from room temperature to 220°C over 1 hour in a nitrogen atmosphere, then heated from 220°C to 240°C over 0.5 hours, and held at 240°C for 10 hours to carry out solid-state polymerization. After the solid-state polymerization, the mixture was cooled to obtain a powdered liquid crystal polyester 2.

[0246] The liquid crystal polyester 2 thus obtained contains Ar 1 60 mol % of repeating units (L1) each having a 1,4-phenylene group, 2 The repeating unit (L2) is 8.0 mol % of a repeating unit having a 1,3-phenylene group, and Ar 2 12 mol % of repeating units (L2) in which R is a 1,4-phenylene group, and Ar 3 The repeating unit (L3) having a 4,4'-biphenylene group accounts for 20.0%. The flow initiation temperature of liquid crystal polyester 2 (LCP2) was 291°C.

[0247] <Preparation of thermoplastic resin> <Preparation of polyethersulfone> The polyethersulfone (PES) used was Sumikaexcel 3600P (manufactured by Sumitomo Chemical Co., Ltd.).

[0248] [Method of measuring length-weighted average fiber length] The length-weighted average fiber length of the fibrous inorganic filler in the resin pellets and in the injection molded product was measured by the following measurement method. (1) First, for the test sample, a brake rotor bell (injection molded product) was cut out from the vicinity of measurement point A of the brake rotor bell shown in Figure 7, measuring 10 mm in width, 10 mm in length, and 10 mm in thickness. In addition, about 5 g of resin pellets were selected. These test samples were sintered in a muffle furnace to remove the resin. The sintering conditions were 500°C and 3 hours. (2) The remaining fibrous inorganic filler was dispersed in 500 mL of an aqueous solution containing 0.05% by volume of a surfactant (Micro90, manufactured by INTERNATIONAL PRODUCTS CORPORATION) to prepare a fibrous inorganic filler dispersion. (3) 50 mL was taken from the 500 mL of fibrous inorganic filler dispersion and filtered under reduced pressure using a φ90 mm Kiriyama funnel filter paper (No. 5C). The fibrous inorganic filler dispersed in the filter paper was observed under a microscope (VH-Z25, Keyence Corporation, magnification 10 to 20x; VHZ-ST, Keyence Corporation, magnification 100x), and five images were taken per sample to create images. (4) All five captured images were binarized using image processing software (WinROOF2018, manufactured by Mitani Shoji Co., Ltd.), and the fiber length of the fibrous inorganic filler was measured using the following method.

[0249] (How to measure the fiber length of fibrous inorganic fillers) (a) The captured image was subjected to monochrome pixelation processing. (b) A binarization process was performed so that only the photographed fibrous inorganic filler was colored. (c) Fiber length was measured using the needle separation function of the image processing software. (d) The fiber lengths of fibrous inorganic fillers that could not be binarized in (c) and curved fibrous inorganic fillers were measured by multi-point measurement. However, in (c) and (d), fibrous inorganic fillers of 10 μm or less were judged as noise when observed at a magnification of 100 times, and fibrous inorganic fillers of 50 μm or less were judged as noise when observed at a magnification of 10 to 20 times, and were not included in the number of fibrous inorganic fillers measured, n. If the number of fibrous inorganic fillers measured, n, did not exceed 500, the procedure returned to (3), and additional images were taken and measurements were continued until n exceeded 500.

[0250] (5) The length-weighted average fiber length lm = (Σli2×ni) / (Σli×ni) was calculated from the fiber lengths of the fibrous inorganic fillers in the five images (Σni>500). li: fiber length of fibrous inorganic filler ni: number of fibrous inorganic fillers with fiber length li

[0251] <Production of resin pellets> <Production of resin pellets 1> As the thermoplastic resin, the above-mentioned liquid crystal polyester 1 (LCP1) was used. As the fibrous inorganic filler, pitch-based carbon fiber (CF1; manufactured by Mitsubishi Chemical Corporation; Dialead (registered trademark) K223HE; cut length 6 mm; tensile strength 3800 MPa; tensile modulus 900 GPa; density 2.20 g / cm 3 ) was used.

[0252] Liquid crystal polyester 1 (LCP1) and pitch-based carbon fiber 1 (CF1) were used in a mixing ratio of 82 parts by mass of pitch-based carbon fiber 1 (CF1) to 100 parts by mass of liquid crystal polyester 1 (LCP1).

[0253] A twin-screw extruder (Ikegai Corporation, "PCM30-HS", cylinder temperature: 380°C, screw rotation speed: 100 rpm) having a main raw material feeder in the upstream section and a side feeder in the downstream section was fed with liquid crystal polyester 1 (LCP1) from the main raw material feeder and pitch-based carbon fiber 1 (CF1) from the side feeder. After melt-kneading, cylindrical resin pellets 1 (length 3 mm) were produced. The length-weighted average fiber length of the pitch-based carbon fiber 1 (CF1) contained in the resin pellet 1 was 192 μm.

[0254] <Production of resin pellets 2> Resin pellets 2 were produced in the same manner as in <Production of resin pellets 1> above, except that PAN-based carbon fiber 2 (CF2; manufactured by Mitsubishi Chemical Corporation; TR03ML A5G; cut length 6 mm; tensile strength 4830 MPa; tensile modulus 250 GPa; density 1.81) was used as the fibrous inorganic filler. The length-weighted average fiber length of the PAN-based carbon fibers 2 (CF2) contained in the resin pellets 2 was 188 μm.

[0255] <Production of resin pellets 3> The thermoplastic resin used was the above-mentioned polyethersulfone 1 (PES1; Sumikaexcel 3600P; manufactured by Sumitomo Chemical Co., Ltd.). As the fibrous inorganic filler, PAN-based carbon fiber 3 (CF3; manufactured by Mitsubishi Chemical Corporation; TR03M; cut length 6 mm; tensile strength 4830 MPa; tensile modulus 250 GPa; density 1.81) was used.

[0256] Polyethersulfone 1 (PES1) and PAN-based carbon fiber 3 (CF3) were used in a blending ratio of 82 parts by mass of PAN-based carbon fiber 3 (CF3) to 100 parts by mass of polyethersulfone 1 (PES1).

[0257] A twin-screw extruder (manufactured by Ikegai Corporation, "PCM30-HS", cylinder temperature: 380°C, screw rotation speed: 100 rpm) having a main raw material feeder in the upstream section and a side feeder in the downstream section was fed with polyethersulfone 1 (PES1) and PAN-based carbon fiber 3 (CF3) from the main raw material feeder, melt-kneaded, and then cylindrical resin pellets 3 (length 3 mm) were produced. The length-weighted average fiber length of the PAN-based carbon fibers 3 (CF3) contained in the resin pellets 3 was 165 μm.

[0258] <Production of resin pellets 4> Resin pellets 4 were obtained as follows using a manufacturing apparatus having the configuration shown in Fig. 6. The extruder used was a GTS-40 type extruder (manufactured by Plastics Engineering Research Institute Co., Ltd.). The belt-type take-up machine used was an EBD-1500A (manufactured by IMEX Co., Ltd.).

[0259] -Process to obtain resin structure The belt-type take-up machine (take-up section 227) was operated at a take-up speed of 10 m / min, and PAN-based carbon fiber 4 (CF4; manufactured by Mitsubishi Chemical Corporation, Pyrofil (registered trademark) CF tow, TR50S15L, tensile strength 4900 MPa, tensile elongation 2.1%, number average fiber diameter 7 μm) was continuously unwound from the fiber roving 20 as a fiber bundle at a take-up speed of 10 m / min, and was first heated to 200° C. and dried in the pre-heating section 221. Separately, the liquid crystal polyester 2 (LCP2) obtained in the above <<Production of liquid crystal polyester 2 (LCP2)>> was heated to 360° C. using the extruder 220 to prepare it into a molten state. Next, while the dried fiber bundle (PAN-based carbon fibers 4) was being supplied to a die (impregnation section 223) attached to the tip of the extruder 220, the molten liquid crystal polyester 2 (resin material M) was fed from the extruder through a supply port 223a of the extruder 220. In the die (impregnation section 223), the liquid crystal polyester 2 was melted at 360°C, and 100 parts by mass of the liquid crystal polyester 2 was impregnated into 67 parts by mass of the PAN-based carbon fibers 4, to obtain a resin structure 23 in which the PAN-based carbon fibers 4 were aligned approximately parallel to the longitudinal direction of the liquid crystal polyester resin layer. Thereafter, the strand-like resin structure 23 that was heated in the die (impregnation section 223) was cooled to 150° C. or lower in the cooling section 225.

[0260] -Pellet obtaining process Next, the strand-like resin structure 23 after cooling was taken up by the belt-type take-up machine (take-up section 227), fed to a pelletizer (cutting section 229), and cut into a length of 12 mm in its longitudinal direction to obtain cylindrical resin pellets 4 (represented as resin pellets 25 in FIG. 6). The length-weighted average fiber length of the PAN-based carbon fibers 4 in the resin pellets 4 was the same as the length of the pellets (12 mm).

[0261] <Production of resin pellets 5> Cylindrical resin pellets 5 were obtained by the same method as in the above <Production of resin pellets 4>, except that the amount of PAN-based carbon fiber 4 was changed and 100 parts by mass of liquid crystal polyester 2 was impregnated into 100 parts by mass of PAN-based carbon fiber 4. The length-weighted average fiber length of the PAN-based carbon fibers 4 in the resin pellets 5 was the same as the length of the pellets (12 mm).

[0262] <Production of resin pellets 6> Cylindrical resin pellets 6 were obtained by the same method as in the above <Production of resin pellets 4>, except that the amount of PAN-based carbon fiber 4 was changed and 100 parts by mass of liquid crystal polyester 2 was impregnated into 25 parts by mass of PAN-based carbon fiber 4. The length-weighted average fiber length of the PAN-based carbon fibers 4 in the resin pellets 6 was the same as the length of the pellets (12 mm).

[0263] <Production of resin pellets 7> Resin pellets 7 were produced in the same manner as in <Production of resin pellets 2> above, except that PAN-based carbon fiber 2 was used in an amount of 67 parts by mass per 100 parts by mass of liquid crystal polyester 1. The length-weighted average fiber length of the PAN-based carbon fibers 2 contained in the resin pellets 7 was less than 1 mm.

[0264] <Production of resin pellets 8> Resin pellets 8 were prepared in the same manner as in <Production of resin pellets 2> above, except that PAN-based carbon fiber 2 was used in an amount of 43 parts by mass per 100 parts by mass of liquid crystal polyester 1. The length-weighted average fiber length of the PAN-based carbon fibers 2 contained in the resin pellets 8 was less than 1 mm.

[0265] <Manufacture of vehicle heating part mounting parts> Example 1 The above-mentioned resin pellet 1 was injection molded using a mold similar to mold 100 shown in Figure 3 under the following injection conditions to produce a brake rotor bell of Example 1 having a shape similar to that of Figure 2 (overall diameter 175 mm; body diameter 130 mm; axial height of the body (thickness of the brake rotor bell) 30 mm; axial thickness of the top wall of the body 5 mm; radial outward projection of the flange from the body 15 mm; axial thickness of the flange 5 mm). Injection conditions: injection molding machine TR450EH3 (manufactured by Sodick Co., Ltd.), mold temperature 100°C, injection speed 200mm / s, plunger temperature 360°C, screw rotation speed (plasticization section) 100rpm, back pressure 0MPa, holding pressure 100MPa, holding time 5 seconds

[0266] The length-weighted average fiber length of the pitch-based carbon fiber 1 (CF1) contained in the brake rotor bell of Example 1 was 155 μm.

[0267] Example 2 The brake rotor bell of Example 2 was manufactured in the same manner as the brake rotor bell of Example 1, except that the above-mentioned resin pellet 2 was used.

[0268] The length-weighted average fiber length of the PAN-based carbon fiber 2 (CF2) contained in the brake rotor bell of Example 2 was 172 μm.

[0269] Example 3 Using the above-mentioned resin pellets 3, the brake rotor bell of Example 3 was manufactured in the same manner as the brake rotor bell of Example 1, except that the mold temperature was changed to 150°C.

[0270] The length-weighted average fiber length of the PAN-based carbon fiber 3 (CF3) contained in the brake rotor bell of Example 3 was 144 μm.

[0271] Example 4 The brake rotor bell of Example 4 was manufactured in the same manner as the brake rotor bell of Example 1, except that the above-mentioned resin pellets 4 were used.

[0272] The length-weighted average fiber length of the PAN-based carbon fiber 4 (CF4) contained in the brake rotor bell of Example 4 was 2.20 mm.

[0273] Comparative Example 1 A brake rotor bell of Comparative Example 1 having the same shape as the brake rotor bells of Examples 1 to 3 was manufactured by processing an aluminum die-cast (ADC12).

[0274] [Evaluation of heat dissipation] The brake rotor bell of each example was placed in a thermostatic chamber and heated to 200°C. After it was confirmed that the brake rotor bell of each example had reached 150°C, it was placed at room temperature. Next, the temperature changes of the body and flange parts of the brake rotor bell of each example placed at room temperature (body part: measured at A in Figure 7, flange part: measured at B in Figure 7) were measured at 0 minutes (immediately after it was confirmed that it had reached 150°C), 10 minutes, 20 minutes, and 30 minutes after the measurements were made. In order to reduce the influence of the installation area during the measurement, the sample was placed on a silicon sponge to insulate the installation area. A contact thermometer (manufactured by Hozan Corporation; product name "DT-510") was used for the measurement. The above heat cycle was carried out five times, and the average value was calculated for each elapsed time. The results are shown in Table 1 as "Heat dissipation (measurement point A) and (measurement point B)".

[0275] [Evaluation of the primary resonance frequency] A piece of aluminum plywood (10 mm x 80 mm x 2 mm) was fixed to the workpiece at the tip of the excitation force detector built into the impedance head of the excitation device (power amplifier / model 371-A) in the impedance device (Ono Sokki Co., Ltd.; mass cancellation amplifier: mass cancellation amplifier MA-5500; channel data station: DS-2100). Each example was positioned so that the center of the brake rotor bell was hooked onto the fixed aluminum plywood. Thereafter, a resonance test was performed using the central excitation method by applying vibration to the tip of the above-mentioned excitation force detector at room temperature (23°C) in the frequency range of 0 to 2000 Hz and detecting the excitation force and acceleration waveform at the excitation point. The mechanical impedance at the excitation point was calculated based on the obtained excitation force and the velocity signal obtained by integrating the acceleration signal, and the frequency at which the first peak was observed on the impedance curve obtained with the horizontal axis representing frequency and the vertical axis representing mechanical impedance was determined as the primary resonant frequency. The results are shown in Table 1 as "primary resonance frequency."

[0276] [Specific heat evaluation] The specific heat of each brake rotor bell was measured in accordance with JIS K7123:2012 using a specific heat analysis program (manufactured by Shimadzu Corporation; product name "DSC-60A Plus"). The results are shown in Table 1 as "specific heat."

[0277] [Evaluation of thermal conductivity] For the brake rotor bell of each example, the thermal conductivity was measured at 23° C. using a xenon flash analyzer (manufactured by Advance Riko Co., Ltd.; product name "TC-7000") in accordance with ASTM E-1461. The results are shown in Table 1 as "thermal conductivity."

[0278] [Table 1]

[0279] The abbreviations in Table 1 have the following meanings: LCP1: Liquid crystal polyester 1 described above LCP2: Liquid crystal polyester 2 mentioned above PES1: Polyethersulfone 1 as described above CF1: Pitch-based carbon fiber 1 described above CF2: PAN-based carbon fiber 2 described above CF3: PAN-based carbon fiber 3 mentioned above CF4: PAN-based carbon fiber 4 mentioned above In addition, since the molding material of the brake rotor bell of Comparative Example 1 was only the above-mentioned aluminum die casting, it is not listed in Table 1.

[0280] FIG. 8 shows the evaluation results of the heat dissipation properties at the measurement point A of the brake rotor bells of Examples 1 to 4 and the brake rotor bell of Comparative Example 1. FIG. 9 shows the evaluation results of the heat dissipation properties at the measurement point B of the brake rotor bells of Examples 1 to 4 and the brake rotor bell of Comparative Example 1. As shown in Figures 8, 9, and Table 1, the temperatures of parts A and B of the brake rotor bells of Examples 1 to 4 after 10 to 30 minutes were lower than those of the brake rotor bell of Comparative Example 1. This confirms that the brake rotor bells of Examples 1 to 4 have high heat dissipation properties despite being made of resin. Moreover, since the brake rotor bells of Examples 1 to 3 have a primary resonance frequency of 260 Hz or higher, it is presumed that they can avoid resonance with road noise more effectively than the brake rotor bell of Comparative Example 1. In addition, since the brake rotor bells of Examples 1 and 2 have a higher primary resonance frequency than the brake rotor bell of Example 3, it is presumed that they can better avoid resonance with road noise.

[0281] [Radioactivity evaluation] Temperature measurement The brake rotor bell of each example was placed in a thermostatic chamber and heated to 200°C. After it was confirmed that the brake rotor bell of each example had reached 150°C, it was placed at room temperature. A contact thermometer (manufactured by Hozan Corporation; product name "DT-510") was used to confirm that the temperature of the brake rotor bell had reached 150°C. Next, the temperatures of the body part (A in FIG. 7) of the brake rotor bell of each example placed at room temperature were measured at 0 minutes (immediately after it was confirmed that it had reached 150°C) and after 10 minutes had passed. In order to reduce the influence of the installation part during the measurement, the sample was placed on a silicon sponge and the installation part was insulated. A contact thermometer (manufactured by Hozan Corporation; product name "DT-510") and a non-contact thermometer (manufactured by Horiba, Ltd.; product name "IT-500L") were used for the measurement. In addition, the measurement using the non-contact thermometer was performed at a distance of 15 cm from the brake rotor bell of each example. The above heat cycle was carried out five times, and the average value was calculated for each elapsed time.

[0282] -Emissivity calculation Next, the emissivity was calculated from the average values ​​of the temperatures measured with the contact thermometer and the non-contact thermometer at 0 minutes and after 10 minutes had elapsed, according to the following formula (e-1). W' is a value calculated from the absolute temperature (T') calculated from the temperature (°C) measured by the non-contact thermometer using the following formula (e-2). W is a value calculated from the absolute temperature (T) calculated from the temperature (° C.) measured by the contact thermometer using the following formula (e-3). In the following equations (e-2) and (e-3), σ is the Stefan-Boltzmann constant (5.67×10−8). Emissivity ε=W' / W···(e-1) W'=σT' 4 (e-2) W = σT 4 (e-3)

[0283] The above-mentioned "temperature measured by a contact thermometer," "temperature measured by a non-contact thermometer," and "emissivity" are shown in Table 2.

[0284] [Table 2]

[0285] As shown in Table 2, it can be seen that the brake rotor bells of Examples 1 to 4 have higher emissivity than the brake rotor bell of Comparative Example 1. Therefore, it is presumed that the brake rotor bells of Examples 1 to 4 had lower temperatures measured by a contact thermometer after 10 minutes than the brake rotor bell of Comparative Example 1.

[0286] (Reference examples 1~7) Multipurpose test pieces (Type A1) of Reference Examples 1 to 7 in accordance with JIS K7139 were produced under the following injection conditions using the thermoplastic resin and inorganic filler shown in Table 3 as molding materials. Test pieces of Reference Examples 1 to 7 were also produced by cutting out test pieces of width 10 mm × thickness 4 mm × length 80 mm from each multipurpose test piece (Type A1). Injection conditions: injection molding machine TR450EH3 (manufactured by Sodick Co., Ltd.), mold temperature 100°C (mold temperature 150°C for only the multi-purpose test piece in Reference Example 5), injection speed 200 mm / s, plunger temperature 360°C, screw rotation speed (plasticization part) 100 rpm, back pressure 0 MPa, holding pressure 100 MPa, holding time 5 seconds.

[0287] The test pieces of each example were measured for specific heat, bending strength (23° C., 150° C.), bending modulus (23° C., 150° C.), and specific gravity. The results are shown in Table 3. The specific heat was measured in the same manner as for the brake rotor bell described above.

[0288] [Evaluation of bending strength (23℃, 150℃) and bending modulus (23℃, 150℃)] Using the test pieces of each example, the bending strength and bending modulus were determined in accordance with JIS K7171 (Plastics - Determination of bending properties) and ISO178. Specifically, a three-point bending test was performed five times on each test piece using an Autograph AG-5000D (manufactured by Shimadzu Corporation) at a test speed of 2 mm / min, a support distance of 64 mm, and an indenter radius of 5 mm at 23°C, and the bending strength and bending modulus were calculated from the average values. In addition, using the attached thermostatic chamber, the temperature was raised to a specified temperature, and the measurement sample was placed in the chamber for about 3 hours. After confirming that the test piece had reached 150°C, a three-point bending test was carried out five times in the thermostatic chamber, and the bending strength and bending modulus were calculated from the average values ​​in the same manner. The obtained bending strength and bending modulus are shown in Table 3.

[0289] [Measurement of specific gravity] The specific gravity of each test piece was determined in accordance with ASTM D792 using an automatic specific gravity measuring device (ASG-320K, manufactured by Kanto Major Co., Ltd.).

[0290] [Table 3]

[0291] The abbreviations in Table 3 have the following meanings: LCP1: Liquid crystal polyester 1 described above PES1: Polyethersulfone 1 as described above CF1: Pitch-based carbon fiber 1 described above CF2: PAN-based carbon fiber 2 described above CF3: PAN-based carbon fiber 3 mentioned above GF1: Glass fiber (manufactured by Nitto Electric Glass Co., Ltd.; E-glass; product name "T781H"; cut length 6 mm) MK1: Mica (manufactured by Yamaguchi Mica Co., Ltd.; product name "A-31S")

[0292] From a comparison between the test pieces of Reference Examples 1 to 6 and the test piece of Reference Example 7, it can be confirmed that the test pieces of Reference Examples 1 to 6 using the fibrous inorganic filler have higher bending strength and bending modulus than the test piece of Reference Example 7 using the plate-like inorganic filler. From this, it is presumed that the mechanical strength is also improved when the fibrous inorganic filler is used in the vehicle heat generating part mounting member of this embodiment, compared to when the plate-like inorganic filler is used.

[0293] (Reference example 8) The above-mentioned resin pellets 5 were loaded into an injection molding machine TR450EH3 (manufactured by Sodick Co., Ltd.) with a molding temperature of 360°C, and injected into a mold with a mold temperature of 100°C at an injection speed of 20 mm / s, a screw rotation speed of 100 rpm, a holding pressure of 50 MPa, and a back pressure of 0 MPa to produce a multipurpose test piece (Type A1) of Reference Example 8 in accordance with JIS K7139, and a flat test piece of Reference Example 8 with a width of 150 mm, length of 150 mm, and thickness of 2 mm, by changing the mold under the same conditions.

[0294] (Reference example 9) A multipurpose test piece (Type A1) for Reference Example 9 and a flat test piece for Reference Example 9 measuring 150 mm wide x 150 mm long x 2 mm thick were prepared in the same manner as in Reference Example 8, except that the above-mentioned resin pellet 4 was used.

[0295] (Reference example 10) A multipurpose test piece (Type A1) of Reference Example 10 and a flat test piece of Reference Example 10 measuring 150 mm wide x 150 mm long x 2 mm thick were prepared in the same manner as in Reference Example 8, except that the above-mentioned resin pellets 6 were used.

[0296] (Reference example 11) A multipurpose test piece (Type A1) of Reference Example 11 and a flat test piece of Reference Example 11 measuring 150 mm wide x 150 mm long x 2 mm thick were prepared in the same manner as in Reference Example 8, except that the above-mentioned resin pellets 7 were used.

[0297] (Reference example 12) A multipurpose test piece (Type A1) of Reference Example 12 and a flat test piece of Reference Example 12 measuring 150 mm wide x 150 mm long x 2 mm thick were prepared in the same manner as in Reference Example 8, except that the above-mentioned resin pellets 8 were used.

[0298] (Reference example 13) A plate test piece for Reference Example 13 having the same shape as the plate test pieces for Reference Examples 8-12, 150 mm wide × 150 mm long × 2 mm thick, was prepared by machining an aluminum die-cast (ADC12).

[0299] [EMI shielding performance evaluation] The shielding characteristics of the flat test pieces of each example against electric and magnetic waves were evaluated by the Advantest method. Specifically, the flat test pieces of each example were placed in a shielding box, and electric and magnetic waves with frequencies of 30 to 1000 MHz were emitted from one side, and the electric and magnetic waves passing through the flat test pieces of each example were received from the other side, and the attenuation of the electric and magnetic waves passing through the flat test pieces of each example was measured as the shielding characteristics (dB). The above measurements were performed using a plastic shielding material evaluation device (product name: TR17301A, manufactured by Advantest Corporation), an EMI test receiver (product name: R&S (registered trademark) ESR3, manufactured by Rohde & Schwarz), and an amplifier (product name: 8447D preamplifier, manufactured by Keysight Technologies) under the following two measurement conditions (measurement conditions X and Y). Note that, for measurement condition Y, only the flat test pieces of Reference Examples 8, 12, and 13 were measured. Regarding the above results, the shielding characteristic values ​​at 30 MHz, 100 MHz, 200 MHz, 300 MHz, 500 MHz, and 1000 MHz are extracted and the EMI shielding characteristic under measurement condition X is shown in Table 4, and the EMI shielding characteristic under measurement condition Y is shown in Table 5. [Measurement condition X] Resolution bandwidth (RBW) 50MHz Video Bandwidth (VBW) 50MHz Sweep time (SWP) 1s [Measurement condition Y] Resolution bandwidth (RBW) 1kHz Video Bandwidth (VBW) 300Hz Sweep time (SWP) 35s

[0300] [Measurement of specific gravity] The specific gravity of each plate test piece was determined in accordance with ASTM D792 using an automatic specific gravity measuring device (ASG-320K, manufactured by Kanto Major Co., Ltd.). The results are shown in Table 4.

[0301] [Evaluation of bending strength and bending modulus] A test specimen measuring 10 mm wide x 4 mm thick x 80 mm long was cut out from each multipurpose test piece (Type A1) of each example to prepare each test piece. The bending strength and bending modulus of the test pieces were determined in accordance with JIS K7171 (Plastics - Determination of bending properties) and ISO178. Specifically, a three-point bending test was performed five times on the test piece using an Autograph AG-5000D (manufactured by Shimadzu Corporation) at a test speed of 2 mm / min, a support distance of 64 mm, an indenter radius of 5 mm, and a temperature of 23° C., and the bending strength and bending modulus were calculated from the average values. The obtained bending strength and bending modulus are shown in Table 4.

[0302] [Evaluation of tensile strength] The tensile strength (MPa) was measured at a test speed of 5 mm / min using the multipurpose test piece (Type A1) of each example in accordance with JIS K7161 (Plastics - Test method for tensile properties) and ISO527. The measurement was performed on 5 samples and the average value was calculated. The measurement device used was an autograph AG-5000D (manufactured by Shimadzu Corporation). The results are shown in Table 4.

[0303] [Table 4]

[0304] The abbreviations in Table 4 have the following meanings: LCP1: Liquid crystal polyester 1 described above LCP2: Liquid crystal polyester 2 mentioned above CF2: PAN-based carbon fiber 2 described above CF4: PAN-based carbon fiber 4 mentioned above

[0305] FIG. 10 shows the evaluation results of the EMI shielding characteristics (dB) of the flat test pieces of Reference Examples 8, 12, and 13 in the electric field waves of each frequency under Measurement Condition X. FIG. 11 shows the evaluation results of the EMI shielding characteristics (dB) of the flat test pieces of Reference Examples 8, 12, and 13 in a magnetic field wave of each frequency under Measurement Condition X.

[0306] 10, 11 and Table 4, it can be confirmed that the flat test specimens of Reference Examples 8 to 10, which have a longer length-weighted average fiber length of the carbon fibers in the pellets, have EMI shielding properties equivalent to that of the flat test specimen of Reference Example 13. From this, it is presumed that the vehicle heat generating part mounting member of this embodiment, which is made of the same molding material, also has good EMI shielding properties. In addition, it can be confirmed that the test pieces of Reference Examples 8 to 12 have good bending strength, bending modulus, and tensile strength. From this, it is presumed that the vehicle heat generating part mounting member of the present embodiment made of the same molding material also has sufficient mechanical strength.

[0307] [Table 5]

[0308] The abbreviations in Table 5 have the following meanings: LCP1: Liquid crystal polyester 1 described above LCP2: Liquid crystal polyester 2 mentioned above CF2: PAN-based carbon fiber 2 described above CF4: PAN-based carbon fiber 4 mentioned above

[0309] FIG. 12 shows the evaluation results of the EMI shielding characteristics (dB) of the test pieces of Reference Examples 8, 12, and 13 in the electric field waves of each frequency under measurement condition Y. FIG. 13 shows the evaluation results of the EMI shielding characteristics (dB) of the test pieces of Reference Examples 8, 12, and 13 in a magnetic field wave of each frequency under measurement condition Y.

[0310] 12, 13 and Table 5, it can be confirmed that the flat test piece of Reference Example 8, which has a longer length-weighted average fiber length of the carbon fibers in the pellet, has EMI shielding properties equivalent to those of the flat test piece of Reference Example 13. From this, it is presumed that the vehicle heat-generating part mounting member of this embodiment, which is made of the same molding material, also has good EMI shielding properties.

[0311] [Evaluation of driving performance] ·Temperature measurement For the brake rotor bells of Example 1 and Comparative Example 1, a running test was carried out in the following manner. The brake rotor bell of Example 1 was attached to the left front wheel of a racing car (manufactured by West Racing Cars Co., Ltd.; product name: "VITA-01"), and the car was driven 10 laps around a circuit course with a circumference of 1.264 km, and the temperature of the brake rotor bell of Example 1 was measured during and after the 10 laps. The weather during the drive was clear, and the temperature was 16°C. In addition, the temperature of the brake rotor bell of Comparative Example 1 during driving and after driving 10 laps was measured in the same manner as above, except that the brake rotor bell of Comparative Example 1 was attached to the left front wheel of a racing car. Temperature measurements were taken using a wireless temperature logger (Advantest, AirLogger TM The measurements were taken using a Type T thermocouple on a WM1000 (model: WM1000-U000-001). The results are shown in Table 6. Moreover, the temperature changes with respect to the running time (s) of the brake rotor bells of Example 1 and Comparative Example 1 are shown in FIG.

[0312] ·Speed ​​measurement The running speed was also measured during the above temperature measurements. The running speed was measured using a data logger (manufactured by Aim Corporation; product name: "SOLO2"). As a result, the average speed up to the fifth lap was 70km / h, and the maximum speed was 116km / h. After the fifth lap and until the tenth lap, the average speed was 72km / h, and the maximum speed was 118km / h.

[0313] [Table 6]

[0314] As shown in Table 6 and FIG. 14, the brake rotor bell of Example 1 had a lower temperature during running (for example, after running 5 laps (around 300 s of running time) and after running 10 laps (around 600 s of running time)) than the brake rotor bell of Comparative Example 1. It was also confirmed that the brake rotor bell of Example 1 can be used as a brake rotor bell for vehicles even though it is made of resin. [Explanation of symbols]

[0315] 1...Brake rotor bell, 10...Base portion, 11...Flange portion 12: first through hole; 13: second through hole; 14: third through hole

Claims

1. A mounting member to be attached to a heat generating portion of a vehicle, The present invention includes an injection-molded article containing a thermoplastic resin and a fibrous inorganic filler, The thermoplastic resin is a liquid crystal polyester or a polyethersulfone, The vehicle heat generating part mounting member, wherein the injection molded product has a primary resonance frequency of 260 Hz or more.

2. The vehicle heat generating part mounting member according to claim 1 , wherein the fibrous inorganic filler is carbon fiber.

3. 3. The vehicle heat generating part mounting member according to claim 1, wherein the content of the fibrous inorganic filler is 30 to 120 parts by mass with respect to the total amount (100 parts by mass) of the thermoplastic resin.

4. The vehicle heat generating part mounting member according to any one of claims 1 to 3, wherein the injection molded product has a specific heat at 23 ° C., measured in accordance with JIS K7123:2012, of 0.92 to 1.50 J / g · K.

5. The vehicle heat generating part mounting member according to any one of claims 1 to 4, wherein the injection molded product has a specific heat at 150 ° C., measured in accordance with JIS K7123:2012, of 1.00 to 2.00 J / g · K.

6. The vehicle heat generating part mounting member according to any one of claims 1 to 5, wherein the injection molded article has a thermal conductivity of 0.20 to 10 W / mK as measured in accordance with ASTM E-1461.

7. The vehicle heat generating part mounting member according to any one of claims 1 to 6, wherein the injection molded product has a primary resonance frequency of 300 to 400 Hz.

8. The vehicle heat generating part mounting member according to any one of claims 1 to 7, wherein the injection molded product has an emissivity of 0.80 or more.

9. The vehicle heat generating part mounting member according to any one of claims 1 to 8, which is used as a peripheral member of a brake rotor.

10. The vehicle heat generating part mounting member according to any one of claims 1 to 9, which is used as a brake rotor bell.

11. A vehicle having a vehicle heat generating part mounting member according to any one of claims 1 to 10 mounted on a heat generating part.

Citation Information

Patent Citations

  • Disk brake, disk brake pad, and back plate for disk brake pad

    JP2001165210A

  • Fixing device

    JP2003084601A

  • Recycled composite material

    JP2007138039A

  • Reduced diameter brake rotors for large vehicles

    JP2017519954A

  • Friction member, friction material composition for lower layer materials, lower layer material, disc brake pad and automobile

    WO2020021647A1